Double layer gas filter and system and method for making same

By uniformly dispersing the nanoparticles in the double-layer filter medium of the gas filter, the problems of low filtration efficiency and short life in the prior art are solved, and efficient and stable filtration performance is achieved.

CN119233849APending Publication Date: 2024-12-31MATIF LUXEMBOURG +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380041722.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-04-08
Filing Date
2023-04-07
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

Existing gas filters are inefficient in capturing submicron particles. Uneven dispersion of nanoparticles leads to the efficiency and life of the filter media, and it is difficult for traditional wet lamination methods to incorporate nanoparticles evenly.

Method used

A double-layer filter media structure is adopted, in which the first and second layers are both incorporated into nanoparticles, and the nanoparticles are evenly distributed in the filter media through specific dispersion and bonding methods, thereby improving filtration efficiency and dust capacity.

Benefits of technology

It significantly improves the filtration efficiency and life of the gas filter, ensures the stability and uniformity of the filtration performance, and extends the service life of the filter.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005143657240000391
    Figure BDA0005143657240000391
  • Figure BDA0005143657240000392
    Figure BDA0005143657240000392
  • Figure BDA0005143657240000393
    Figure BDA0005143657240000393
Patent Text Reader

Abstract

Filtration media and filters are provided that include at least two layers, and a plurality of nanoparticles dispersed at a depth within at least one layer. A gas filter includes a first layer of fibers, a second layer of fibers bonded to the first layer, and a plurality of nanoparticles incorporated into the first layer. The nanoparticles increase the total surface area within the filter, which increases its filtration efficiency and allows the capture of submicron contaminants without significantly compromising other factors, such as pressure drop through the filter (i.e. Air flow). Further, the filters disclosed herein can withstand strict conditioning, which enables the filters to achieve the same level of filtration performance throughout its service life. Systems, devices, and methods for making such filters are also provided.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims the benefit of U.S. Provisional Application Serial No. 63 / 329,146, filed April 8, 2022, the entire disclosure of which is incorporated herein by reference for all purposes. This application is also related to commonly assigned, co-pending U.S. Provisional Patent Application Serial Nos. 63 / 329,009, 63 / 328,983, 63 / 328,998, 63 / 328,970, 63 / 328,959, 63 / 329,018, 63 / 329,137, 63 / 329,155, 63 / 329,158, 63 / 329,161, and 63 / 329,162, all filed April 8, 2022, the entire disclosures of which are incorporated herein by reference in their entirety for all purposes. Technical Field

[0003] The present description generally relates to gas filters having at least two layers, at least one of which incorporates nanoparticles, and systems and methods for making such gas filters. Background Art

[0004] Because of the fine fiber size of fibrous materials, they are particularly useful for capturing contaminants in filtration devices. The fibers of filter media are measured in microns and can be formed by spunbonding, meltblowing, electrospinning or other techniques. As fluid flows through the filter media, the fine fibers capture and retain contaminants in the filter media.

[0005] The two main types of filtration devices that incorporate fibrous materials include surface filters and depth filters. Surface filters (e.g., membrane layers or films) act as a barrier to capture contaminants before they enter the media structure. These surface filters typically have submicron pore sizes and narrow pore size distributions. Surface filters tend to have relatively high particle capture efficiencies. However, they also have relatively high pressure drops and low dust holding capacities. High pressure drops result in reduced air flow through the filter. Low dust holding capacities significantly reduce the life of the filter. As a result, surface filters have limited application in the air filtration industry.

[0006] Depth filters are commonly used in air filtration units with medium to high efficiency, low pressure drop, and relatively high dust holding capacity. Traditional residential and commercial air filters, such as HEPA filters, are generally rated based on the filter's ability to capture particles ranging from approximately 0.3 to 10 microns. This rating is called the Minimum Efficiency Reporting Value, or MERV, and is established by the American Society of Heating, Refrigerating and Air-Conditioning Engineers (ASHRAE). MERV ratings range from 1-16, with higher values ​​indicating greater efficiency in capturing specific types of particles.

[0007] Pollutants come in a wide range of sizes. However, pollutants smaller than 1 micron are the most harmful particles to the human body and are relatively difficult to filter. For example, traditional mechanical air filters typically report a MERV rating of about 8-10 for fiber filter materials. Therefore, these filter media typically do not capture submicron particles, such as viruses and other harmful pathogens.

[0008] The filtration industry has focused on two different methods of capturing these submicron particles: electrostatic forces and utilizing nanoparticles in the filter media. Electrostatic filters are formed by electrostatically charging the fibers within a fibrous material using triboelectric methods, corona discharge, hydrocharging, electrospinning, or other known methods. Electrostatic filters are most effective at capturing submicron particles, fairly effective at capturing particles between 1 and 3 microns, and least effective at capturing larger particles between 3 and 10 microns. Electrostatic fibers are commonly used in many filtration applications, such as face masks and HEPA filters, to filter submicron contaminants, such as viruses, etc.

[0009] One disadvantage of electrostatic filters is that the electrostatic charge decays over time and with filter use. As a result, the filter's efficiency decreases relatively quickly, shortening its life. For example, an electrostatic filter with an initial MERV rating of 13 may lose at least 2-3 MERV rating points after the electrostatic force decays. This compromises the integrity of the filter and may partially or completely inhibit its ability to capture submicron particles.

[0010] Another approach to capturing submicron contaminants is to use nanoparticles in combination with fibers. A filtration system may employ a filter media that includes relatively large fibers with diameters measured in microns and relatively small nanoparticles. The nanoparticles increase the surface area within the media for capturing particles by reducing the overall fiber size within the media. The nanoparticles also tend to collapse onto each other, increasing the packing density within the filter media. It has been shown that even a small number of nanometer-sized fibers in a layer formed on a microfiber material can improve the filtration characteristics of the material.

[0011] The most common method of incorporating nanoparticles into filter media is to apply a thin layer of continuous nanofibers to a non-manufactured substrate by electrospinning. The nanoparticles typically extend parallel or perpendicular to the surface of the bulk filter media layer, providing high efficiency filtration of small particles in addition to the filtration of larger particles provided by the coarse filter media. For example, U.S. Patent No. 6,743,273 discloses a filter media in which a continuous nanofiber layer is deposited on the surface of a substrate. U.S. Patent No. 10,799,820 also discloses an air filter media comprising a continuous nanofiber layer on the surface of the filter media.

[0012] While existing filter media incorporating nanoparticles have improved the relative efficiency of these filters, the commercial potential of these filters in certain applications is limited because the nanoparticles are typically dispersed on the surface of the nonwoven material. The relatively thin layer of nanoparticles on the filter surface provides only limited particle filtration and has a relatively low dust holding capacity.

[0013] Although many attempts have been made to incorporate nanomaterials into filter media to improve overall filtration efficiency, these attempts have been limited to so-called "wetlaid" methods. These wetlaid methods involve incorporating short-cut nanofibers into a liquid slurry to separate entangled nanofibers with the aid of a surfactant. For example, U.S. Patent No. 10,252,201 discloses a filter medium made of a mixture of short-cut nanofibers and short-cut coarse fibers formed by a wet-laid method. Similarly, U.S. Patent Application No. 2021 / 0023813 discloses a method for producing a composite structure consisting of a continuous fiber nonwoven substrate and discontinuous fibers (e.g., carbon nanofibers). The method includes pulling a continuous fiber nonwoven substrate through a slurry of discontinuous fibers, wherein the nanomaterial is embedded in the nonwoven substrate.

[0014] While these structures have shown improved efficiency, they also suffer from other issues such as reduced life and / or efficiency when the media is placed under normal use conditions. Additionally, these wet-laid methods have not been successful in incorporating the nanoparticles uniformly throughout the nonwoven material, which results in agglomeration of the nanoparticles within the material, further reducing its efficiency and overall dust holding capacity.

[0015] Therefore, there is a need for improved gas filters and systems and methods for making such filters. It is particularly desirable to incorporate nanoparticles into at least a portion of the overall gas filter to improve the performance characteristics of the filter. Summary of the invention

[0016] A brief overview of the claimed subject matter is presented below to provide a basic understanding of some aspects of the claimed subject matter. This summary is not a comprehensive overview of the claimed subject matter. It is neither intended to identify the key or important elements of the claimed subject matter nor to describe the scope of the claimed subject matter. Its sole purpose is to present some concepts of the claimed subject matter in a simplified form as a prelude to the more detailed description presented later.

[0017] Provided are filter media and filters, such as air filters, masks, gas turbine and compressor intake filters, panel filters, etc., comprising at least two layers and a plurality of nanoparticles dispersed at a certain depth in at least one layer. Also provided are systems, devices, and methods for making such filters.

[0018] In one aspect, a gas filter comprises a first layer of fibers, a second layer of fibers bonded to the first layer, and a plurality of nanoparticles incorporated into the first layer. The nanoparticles increase the total surface area within the filter, which increases its filtration efficiency and allows for the capture of submicron contaminants without significantly compromising other factors, such as pressure drop (i.e., air flow) through the filter. In addition, the filters disclosed herein are able to withstand rigorous conditioning, which allows the filter to achieve the same level of filtration performance throughout its service life.

[0019] The first layer of the gas filter defines a first surface and a second surface opposite to the first surface. The nanoparticles are arranged through the first surface and enter the internal structure between the first and second surfaces of the first layer. In certain embodiments, the nanoparticles are "dispersed at a certain depth" in the first layer. As used herein, the term "at a certain depth" means that the nanoparticles are dispersed across the first surface of the layer so that at least some of the nanoparticles are arranged in the internal structure between the first and second relative surfaces of the layer or filter medium. In certain embodiments, the nanoparticles are dispersed substantially throughout the entire medium from the first surface to the relative second surface. In other embodiments, the nanoparticles are dispersed in a portion of the medium from the first surface to the position between the first and second surfaces. In other embodiments, the nanoparticles are arranged with a density gradient from the first surface of the substrate to the relative second surface. The density of the nanoparticles can be larger at the first surface or the second surface.

[0020] The second layer of the gas filter can be bonded to the first surface or the second surface of the first layer. In certain embodiments, a plurality of nanoparticles are also incorporated into the second layer. The nanoparticles can be dispersed throughout the internal structure of the second layer. The nanoparticles can be arranged in a density gradient from one surface of the second layer to another surface. In this embodiment, the density of the nanoparticles on the dispersed surface (that is, the surface into which the nanoparticles are dispersed) will be greater than the density of the opposite surface of the second layer.

[0021] The first layer and the second layer can be bonded to each other so that their dispersion surfaces face each other (i.e., wherein the larger density of nanoparticles is located on the inner side of the gas filter). Alternatively, the first layer and the second layer can be bonded to each other so that their dispersion surfaces face away from each other so that the larger density of nanoparticles is located on the outer side of the gas filter. In yet another embodiment, the dispersion surfaces alternate so that the larger density of nanoparticles of one layer is located on the inner side of the gas filter, while the larger density of nanoparticles of another layer is located on the outer side of the gas filter.

[0022] On the other hand, the linear density of the first layer of the gas filter can be greater than about 3 deniers. The linear density of the fibers in the air filter is generally about 3 deniers or less to ensure that the fibers are small enough to capture pollutants passing through the filter. Applicants have unexpectedly discovered that by using nanoparticles dispersed in the filter media, the fibers can have a greater linear density, for example, greater than 3 deniers. This is because the nanoparticles provide significant filtering capabilities. In some cases, the linear density of the fibers can be greater than 3 deniers, 5 deniers or greater, 6 deniers or greater, or as large as 7-10 deniers.

[0023] Applicants have also discovered that in some applications, fibers having a linear density greater than that used in conventional filters (e.g., greater than about 3 denier) provide more open space or pores within the filter media, which allows a greater density of nanoparticles to be dispersed therein. While this may be counter-intuitive to one skilled in the art, Applicants have discovered that incorporating nanoparticles into fibers having a greater linear density actually improves the overall efficiency of the filter.

[0024] In certain embodiments, the filter medium may include at least two different fiber thicknesses or linear densities to provide at least two different filter layers in the same filter medium. For example, in some cases, the first layer of the filter will include nanoparticles and a linear density greater than 3 deniers (e.g., 5 deniers or greater or 6 deniers or greater) of fiber. The second layer of the filter medium will contain a linear density of 3 deniers or less of fiber. This double-layer filter medium creates a first filter layer and a second filter layer, the first filter layer mainly uses nanoparticles with a high density in the fiber of a larger thickness to filter pollutants; the second filter layer mainly uses fibers with a lower linear density to filter pollutants, but both parts can contain nanoparticles dispersed throughout the fiber. In certain embodiments, the filter may include three or more separate parts or layers, each with a different denier fiber range.

[0025] The first layer and the second layer may comprise any substrate, such as a sheet, layer, film, apertured film, net, mesh or other medium. In certain embodiments, the substrate will comprise a fibrous material having a structure of interlaced individual fibers or lines. Examples of suitable fibrous materials include, but are not limited to, fibers, layers or webs of meltblown, spunbonded, bonded combed, airlaid, coformed, hydraulically entangled, etc. In other embodiments, knitted fabrics or braided fabrics are envisioned as substrates.

[0026] In some embodiments, the filter includes one or more support layers bonded to the filter medium. The support layer and / or the filter medium may include nanoparticles dispersed within the layer at a certain depth. In some embodiments, a polymer layer, a membrane layer, or a membrane is provided that includes one or more holes for gas or liquid to flow therethrough, wherein the nanoparticles are arranged within the polymer layer at a certain depth.

[0027] In another aspect, a system for making a double-layer filter includes: a feeder for advancing a first layer of fibers from an upstream end to a downstream end; and a dispersion device between the upstream end and the downstream end for dispersing nanoparticles into a first surface of the first layer so that the nanoparticles at least pass through the first surface of the first layer. The system also includes a device for bonding the first layer to a second layer of fibers.

[0028] In certain embodiments, the system includes a second feeder for advancing the second layer of fiber. The first and second feeders may include, for example, a winding device, which feeds the layer to a connection point by the system, and then bonds the two layers together at the connection point. The layers may be bonded together by any suitable method known in the art (for example, mutually laminated). In certain embodiments, the feeder may also be included in a support surface extending between two winders for supporting the fiber layer when substrate moves downstream through the system. In other embodiments, substrate is unwound to the winder directly from an unwinder, without the need for other support surfaces.

[0029] In certain embodiments, the system includes a second dispersing device for dispersing the nanoparticles into the first surface of the second layer so that the nanoparticles pass through at least the first surface of the second layer. The first and second feeders can be configured so that the first surface of the first layer is bonded to the first surface of the second layer. In other embodiments, the first and second feeders are configured so that the second surface of the first layer opposite to the first surface of the first layer is to the second surface of the second layer opposite to the first surface of the second layer. Optionally, the first and second feeders are configured so that the first surface of the first layer is bonded to the second surface of the second layer opposite to the first surface of the second layer.

[0030] The system may also include a fibrotic device for separating and / or isolating nanoparticles in fluid or gaseous medium. As used herein, the term "fibrotic" means that nanoparticle clusters, agglomerates or other groups are transformed (for example, opened, separated, isolated and / or individualized) into at least one single nanoparticle of a size less than 1 micron. In one embodiment, nanoparticles are separated or isolated in suitable gaseous medium (for example air, helium, nitrogen, oxygen, carbon dioxide etc.), and are dispersed in product, substrate or fiber stream via air flow, aerosol, evaporator, spray or other suitable conveying mechanisms. Single nanoparticles are separated and / or isolated in gaseous medium, then dispersed in substrate or air flow, so that nanoparticles are more evenly distributed throughout the layer of gas filter.

[0031] The second device may further include a negative pressure source or vacuum source arranged below the substrate opposite to the first and / or second nozzles to increase the penetration depth and uniformity of the nanoparticles. The negative pressure source may be any suitable suction device that allows the nanoparticles to pass through the substrate, such as a suction pump, etc.

[0032] The system may also include a coating device for distributing adhesive to the fiber in the first layer and / or the second layer. Adhesive may comprise various conventional materials, including natural-based materials, such as starch, dextrin, guar gum, etc., or synthetic resins, such as EVA, PVA, PVOH, SBR, polyglycolide, etc. In some embodiments, substrate comprises its own adhesive composition. In these embodiments, adhesive or bonding material may be added or may not be added to substrate. In such an embodiment, substrate comprises biocomponent fiber, wherein one of the components comprises at least partially an outer sheath around an inner core.

[0033] The second device may further include a dryer, such as an IR oven or the like, disposed near the downstream end of the feeder for heating the nanoparticles and the fibers to bond the nanoparticles to the fibers within the substrate.

[0034] In another aspect, a method for making a dual-layer filter includes providing a first layer and a second layer each comprising fibers; dispersing nanoparticles into a first surface of the first layer such that the nanoparticles pass through at least the first surface of the first layer; and bonding the first layer to the second layer to form a filter medium.

[0035] In certain embodiments, the method further comprises dispersing the nanoparticles into the first surface of the second layer so that the nanoparticles at least pass through the first surface of the second layer. The first surface of the first layer can be bonded to the first surface or the second surface of the second layer. Alternatively, the second surface of the first layer can be bonded to the first surface or the second surface of the second layer.

[0036] The nanoparticles can be separated or isolated in a fluid or gas medium and then dispersed substantially throughout the first layer and / or the second layer of the gas filter. In some embodiments, the nanoparticles can form a gradient within the first layer and / or the second layer such that the density of the nanoparticles decreases from one surface to another.

[0037] Adhesive can be applied to the fiber in the first layer and / or the second layer to retain the nanoparticles in the layer. The adhesive can comprise various conventional materials, including natural-based materials, such as starch, dextrin, guar gum, etc., or synthetic resins, such as EVA, PVA, PVOH, SBR, polyglycolide, etc. In some embodiments, the substrate comprises an adhesive composition itself. In these embodiments, adhesive or bonding material may or may not be added to the substrate. In such an embodiment, the substrate comprises biocomponent fibers, wherein one of the components comprises an outer sheath at least partially around the inner core.

[0038] The recitation herein of desirable objectives met by various embodiments of the specification is not intended to imply or represent that any or all of these objectives are present as essential features (either individually or collectively) in the most general embodiment of the specification or in any of its more specific embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 is a side view of a fiber material having nanoparticles dispersed throughout a portion of the material;

[0040] Figure 2 is a side view of a fiber material having nanoparticles dispersed throughout the material;

[0041] Figure 3 is a side view of a fiber material having nanoparticles dispersed within the material in a gradient manner;

[0042] Figure 4 A double layer of filter media is shown;

[0043] Figures 5A-5C Biocomponent fibers incorporated into a fibrous material are shown;

[0044] Figure 6 A pleated fiber filter media is shown;

[0045] Figure 7 A representative air filter is shown;

[0046] Figure 8 A gas filter having first and second support membrane layers and a filter medium is shown;

[0047] Fig. 9A and 9BAn apertured membrane used as a support membrane layer is shown;

[0048] Figures 10A-10E Various embodiments of open-pore films having nanoparticles incorporated into the film are shown;

[0049] Fig.11 A gas filter is shown;

[0050] Fig.12 A system for producing a fibrous material within a substrate is schematically shown;

[0051] Fig.13 A system for converting nanofiber clusters into individual nanoparticles is schematically shown;

[0052] Figures 14A-14C The photos are large nanofiber clusters, small nanofiber clusters and single nanoparticles.

[0053] Fig.15 Shows Fig.13 The system's injectors;

[0054] Fig.16 Shows Fig.13 The reactor of the system;

[0055] Fig.17 Another embodiment of a system for converting nanofiber clusters into individual nanoparticles is shown;

[0056] Fig.18 A system for producing a double-layer fiber material is shown;

[0057] Fig.19 shows a fiber material having nanoparticles dispersed within the material at a depth;

[0058] Fig. 20 A fiber material having nanoparticles dispersed within the material at a depth and a scrim layer covering the nanoparticles is shown;

[0059] Fig.21 A two-layer fiber material having nanoparticles dispersed on the inner surfaces of both layers is shown;

[0060] Fig. 22 An alternative embodiment of a system for producing a fibrous material in a fluid stream is shown;

[0061] Fig.23A is a photograph of the fiber material without the use of a binder;

[0062] Fig. 23B is a photograph of a fibrous material having a binder;

[0063] Fig.24Ais a photograph of a fibrous material having nanoparticles dispersed throughout the material in the form of clumps or clusters; and

[0064] Fig. 24B is a photograph of a fibrous material having nanoparticles substantially uniformly dispersed throughout the material. DETAILED DESCRIPTION

[0065] This specification and the accompanying drawings illustrate exemplary embodiments, and should not be considered as limiting, and the claims define the scope of this specification, including equivalents. Without departing from the scope of this specification and the claims, various mechanical, composition, structural and operational changes can be made, including equivalents. In some cases, well-known structures and technologies have not yet been shown or described in detail, so as not to make the description unclear. The same numbers in two or more figures represent the same or similar elements. In addition, as long as feasible, the elements and related aspects described in detail with reference to an embodiment can be included in other embodiments that are not specifically shown or described. For example, if an element is described in detail with reference to an embodiment, and it is not described with reference to a second embodiment, the element can still be claimed to be included in the second embodiment. In addition, the description herein is for illustrative purposes only and does not necessarily reflect the actual shape, size or size of the system or the components shown.

[0066] It should be noted that, as used in this specification and the appended claims, the singular forms "a," "an," and "the," as well as any word used in the singular, include plural referents unless clearly and unambiguously limited to one referent. As used herein, the term "include" and its grammatical variations are intended to be non-limiting, such that recitation of items in a list does not exclude other like items that can be substituted or added to the listed items.

[0067] Unless otherwise indicated, any quantitative values ​​are approximate, whether or not stated with the word "about" or "approximately." The materials, methods, and examples described herein are illustrative only and not intended to be limiting.

[0068] Provided are filter media and filters, such as air filters, masks, gas turbine and compressor intake filters, panel filters, etc., comprising at least two layers and a plurality of nanoparticles dispersed at a certain depth in at least one layer. Also provided are systems, devices, and methods for making such filters.

[0069] As used herein, the term "nanoparticle" means any particle having a size less than 1 micron in at least one axis or dimension. For example, a fiber having a diameter or width less than 1 micron and a length greater than 1 micron is a nanoparticle as used herein.

[0070] In certain embodiments, each individual nanoparticle can be a small particle, and its size range is about 1 to about 1000 nanometers, preferably about 1 to about 650 nanometers. In the number size distribution, the particle size of at least half of the particles can be measured as 100 nanometers or below. Most of nanoparticles are usually only composed of hundreds of atoms. As the size of nanoparticles approaches atomic scale, material properties change. This is due to the increase in surface area and volume ratio, causing the surface atoms of the material to dominate the material properties. Due to the very small size of nanoparticles, compared with bulk materials (such as powders, plates, sheets or larger fibers), the surface area of ​​nanoparticles is very large compared to volume. This feature makes nanoparticles have undesirable optical, physical and chemical properties, because they are small enough to limit their electronics and produce quantum effects.

[0071] In some embodiments, the nanoparticles comprise nanofibers having at least one dimension (i.e., diameter, width, height, etc., depending on the cross-sectional shape of the fiber) less than 1 micron. The nanofibers may have continuous lengths, or the nanofibers may have discrete lengths, such as 1 to 100,000 microns, preferably about 100 to 10,000 microns.

[0072] In certain embodiments, filter medium is a nonwoven substrate, which comprises a single fiber or a structure of lines that are interwoven, interlocked or bonded together. Nonwoven fabrics can include sheets or web structures bonded together by mechanical, thermal or chemical means to entangle fibers or filaments (and by perforated membranes). They can be substantially flat porous sheets, which are directly made of independent fibers or molten plastics or plastic films. The example of suitable nonwoven material includes but is not limited to fibers, layers or webs of meltblowing, spunbond or spunlace, thermal bonding, bonding combing, air-laid, wet-laid, co-molding, acupuncture, stitching, hydraulic entanglement, etc.

[0073] In certain embodiments, substrate can comprise knitting and / or woven material. Knitted material can comprise any knitting pattern suitable for desired application. Knitted material suitable for filter application comprises weft knitting, warp knitting, knitted mesh, compressed knitted mesh etc. Woven material suitable for filter application comprises textile filter media, such as monofilament fabric, multifilament fabric, nylon net, polyester net, polypropylene net etc. Woven textile can be used for such as mesh filter press filter cloth, woven filter pad and other die-cutting parts, centrifuge filter bag, liquid filter bag, dust collector filter bag, bed dryer filter bag, rotary drum filter, filter belt, leaf filter, roll medium etc.

[0074] In some embodiments, the fibrous material may include a structure comprising mixed or entangled chopped fibers and / or filaments. As used herein, chopped fibers refer to fibers of limited length. As used herein, filaments refer to fibers with substantially continuous length. In some embodiments, the substrate may include chopped coarse fibers, microfibers, and / or fine fibers. As used herein, "fine fibers" refer to fibers with a diameter less than 1 micron, "coarse fibers" refer to fibers with a diameter greater than 10 microns, and microfibers are synthetic fibers with a diameter less than 10 microns.

[0075] In certain embodiments, the nanoparticles are dispersed in the substrate "at a certain depth". As used herein, the term "at a certain depth" means that the nanoparticles are dispersed across the first surface of the substrate so that at least some of the nanoparticles are disposed between the first and second opposing surfaces in the internal structure of the substrate or medium. In certain embodiments, the nanoparticles are dispersed throughout the substantially entire medium from the first surface to the opposing second surface. In other embodiments, the nanoparticles are dispersed in a portion of the medium from the first surface to a position between the first and second surfaces.

[0076] In some embodiments, the nanoparticles are three-dimensionally distributed in space relative to the supporting fibers, which can increase the fiber surface area and microvolume within the fiber material. The three-dimensional distribution can also prevent complete clogging of specific portions of the fiber material, which is particularly useful in filter media because it allows fluids (e.g., air and other gases) to pass through the filter, thereby reducing the overall pressure drop across the filter.

[0077] In other embodiments, the nanoparticles are arranged with a density gradient across the thickness of the substrate, so that the density of the nanoparticles arranged near a surface is higher than the relative surface, or compared with the middle portion of the substrate, the density of the nanoparticles arranged on the surface is higher. The density gradient shown can be substantially linear, it can be reduced in the form of a series of discrete steps, or the gradient can be random (that is, the reduction of density is usually not linear or step-wise). This density gradient provides many advantageous features (as described below) for certain applications (such as filters).

[0078] Nanoparticles can include any suitable material, such as glass, biosoluble glass, ceramic materials, acrylic, carbon, metals (e.g., alumina), polymers (e.g., nylon, polyethylene terephthalate, etc.), polyvinyl chloride (PVC), polyolefins, polyacetals, polyesters, cellulose ethers, polyalkylene sulfides, poly(arylene oxides), polysulfones, modified polysulfone polymers and polyvinyl alcohol, polyamides, polystyrene, polyacrylonitrile, polyvinylidene chloride, polymethyl methacrylate, polyvinylidene fluoride, and any combination thereof.

[0079] In some embodiments, the nanoparticles can be made into bicomponent segmented cakes and islands. Then, the filaments are stretched to obtain submicron filaments. The continuous filament nanofibers are cut according to the desired length (preferably about 100 to about 10,000 microns).

[0080] In some embodiments, nanoparticles are absorbents and adsorbents. In some embodiments, nanoparticles are activated carbon fibers or activated carbon powder. In some embodiments, nanoparticles are catalytic particles or catalytic fibers. In some embodiments, nanoparticles can be obtained by feeding submicron fiber nonwovens to pulverizer or crusher or trimmer, wherein the bonded nonwoven enters, and obtains short-cut fibers. For example, low weight biocomponent melt-blown or nano melt-blown fabrics can be fed to pulverizer, and submicron nanoparticles can be obtained.

[0081] In some embodiments, different nanoparticles can be mixed. For example, nanofibers and nanobeads can be mixed. Two different nanofibers with different melting points can also be mixed so that the nanoparticles with a lower melting point can serve as a binder for the nanofibers with a higher melting point. Nanoparticles with different diameters and different lengths can also be mixed.

[0082] In some embodiments, the nanoparticles are selected from environmentally sustainable raw materials. The nanoparticles may include biosoluble glass nanofibers, biodegradable nanoparticles, compostable nanoparticles, or recyclable compositions.

[0083] Different types of nanoparticles can be combined. Some nanoparticles can be functional nanoparticles. For example, functional nanoparticles can include activated carbon and / or antibacterial materials deposited on the fibers in the nonwoven material and / or attached to the fibers in the fibrous material. This can improve the gas absorption efficiency of the fiber and the effectiveness of killing bacteria. In addition, nonwoven products of microfiber nonwovens deposited with glass and carbon nanoparticles will provide filtering and deodorizing functions as filter media.

[0084] In some embodiments, nanoparticles are bonded to fibers by mechanical entanglement. This mechanical bonding can be supplemented with adhesives or bonding agents, as discussed in more detail below. In certain embodiments, nanoparticles are not curled (that is, they do not include the obvious wavy, curved, curled, coiled sawtooth or similar shapes associated with the nanoparticles in a relaxed state). In other embodiments, nanoparticles can have a coiled body structure with discrete lengths. For example, when these coiled nanofibers with discrete lengths are attached to fibers, they tangle with each other, and are also firmly attached to fibers, attached to fibers and attached to fibers around fibers, thereby forming modified fibers. In other embodiments, the attachment of nanofibers to microfibers is achieved by attracting static charge and / or van der Waals forces between fibers and nanoparticles.

[0085] Also provided are filter media and filters, such as air filters, masks, gas turbine and compressor intake filters, panel filters, etc., which include nanoparticles dispersed in the filter media at a certain depth. In some embodiments, the filter includes one or more support layers bonded to the filter media. The support layer and / or the filter media may include nanoparticles dispersed in the layer at a certain depth. In some embodiments, a polymer layer, a membrane layer or a membrane is provided, which includes one or more holes for gas or liquid to flow therethrough, and the nanoparticles are arranged in the polymer layer at a certain depth. In other embodiments, the fibrous material includes a flexible surface layer for finger bandage pads, masks, etc.

[0086] Provided herein are systems, devices and methods for producing fibrous materials and products containing fibrous materials (e.g., gas filters). Also provided are systems and methods for isolating individual nanoparticles in a gaseous medium (e.g., air, helium, nitrogen, oxygen, carbon dioxide, etc.) (rather than a liquid) and being able to be dispersed into another product, film, layer or substrate by airflow, aerosol, evaporator, spray or other suitable delivery mechanism.

[0087] Although the following description is mainly directed to fiber materials and filter media, it should be understood that the devices and methods disclosed herein can be easily adapted to various other applications. For example, the fiber materials disclosed herein can be used in household cleaning products, roofing and flooring products, automotive interiors and headliners, reusable bags, wall coverings, filtration devices, insulation materials, etc. In addition, the single nanoparticles isolated and generated in the methods described herein can be used in various coatings, composite materials and / or additives, for example, polymers, food packaging, flame retardants, fuel cells, batteries, capacitors, nanoceramics, lamps, material manufacturing, production methods, reinforcements for composite materials, cements and other materials, medical diagnostic applications, medical treatment devices or therapies, tissue engineering (e.g., scaffolds for bone or tissue repair), drinking water, industrial process fluids, food and beverage products, drugs and biologics, tissue imaging, medical treatment delivery, environmental applications (e.g., biodegradable compounds), etc.

[0088] Figure 1A fibrous material or substrate 10 including a plurality of fibers 12 and nanoparticles 14 is shown. The substrate 10 has a first surface 16 and a second surface 18 opposite the first surface 16, and defines a width or thickness between the first and second surfaces 16, 18. The nanoparticles 14 have been deposited into the substrate through the first surface 16. As shown, the nanoparticles 14 penetrate through the first surface 16 to the "depth" between the first and second surfaces 16, 18 of the substrate 10. In some embodiments, the nanoparticles 14 penetrate from the first surface to at least 25% of the width or thickness between the first and second surfaces 16, 18, or more preferably penetrate to at least about 50% of the thickness. In other embodiments, the nanoparticles 14 penetrate substantially the entire substrate 10 from the first surface 16 to the second surface 18.

[0089] Nanoparticles 14 preferably include individual nanoparticles (e.g., nanoparticles) that have been broken, separated, and isolated from one another prior to being dispersed into substrate 10. Fig. 24B As shown in FIG. 1 , the nanoparticles 14 are not present in the fiber product in the form of a layer, and there are no obvious nanofiber agglomerates or bundles (such as Fig.24A This allows the nanoparticles to be more dispersed throughout the substrate, which in some applications (e.g., gas filters) provides a more effective filtration capability to filter out pollutants. In addition, this allows the nanoparticles in the fibrous material to have a greater areal density (in grams per square meter (gsm)) or "addition amount" within the material. The term "addition amount" as used herein means the areal density (gsm) of a material, fiber, or particle in a thin layer, sheet, or film of a material.

[0090] In certain embodiments, the nanoparticles may comprise about 0.1 g / m 2 About 20 g / m 2 , preferably at least about 2.0 g / m 2 The specific amount of addition or surface density may depend on the application. For example, the applicant has found that a higher surface density or addition will increase the efficiency of the fiber material in filtering pollutants. Therefore, the specific amount of nanoparticles added may depend on the desired efficiency of the filter medium.

[0091] Figure 2 A fibrous material or substrate 20 is shown that includes a plurality of fibers 12 and nanoparticles 14. As shown, the nanoparticles 14 penetrate throughout the entire width of the substrate 20 from the first surface 16 to the second surface 18. In certain embodiments, the nanoparticles 14 are substantially dispersed throughout the fibers 12 of the substrate, such as Figure 2In some embodiments, the density of nanoparticles located at the first surface 16 differs from the density of nanoparticles dispersed in the central portion of the substrate 20 between the surfaces 16, 18 by less than 50%. In some embodiments, the difference is less than 25%, preferably less than 10%. In some embodiments, the amount or number of individual nanoparticles dispersed in the central portion of the substrate 20 is at least about 50%, preferably at least about 75%, and more preferably at least about 90% of the amount of individual nanoparticles dispersed at or near the first surface 16.

[0092] In other embodiments, the nanoparticles 14 are arranged in a density gradient from the first surface 16 to the second surface 18. For example, Figure 3 A substrate 30 is shown in which the nanoparticles 14 form a density gradient, wherein the density of the nanoparticles 14 disposed near the first surface 16 is higher than the density of the nanoparticles 14 disposed near the second surface 18. In certain embodiments, the difference between the density of the nanoparticles located at the first surface 16 and the density of the nanoparticles dispersed at the second surface 18 is greater than about 75%. In some embodiments, the difference is greater than 50%. In some embodiments, the difference is greater than 25%. In certain embodiments, the amount or number of individual nanoparticles dispersed at or near the second surface 18 is less than about 50%, preferably less than about 25%, and more preferably less than about 10% of the amount of individual nanoparticles dispersed at or near the first surface 16.

[0093] Figure 3 The density gradient shown in FIG. 1 may be substantially linear from the first surface 16 to the second surface 18. Alternatively, the density of the nanoparticles 14 may decrease from the first surface 16 to the second surface 18 in a series of discrete steps, or the gradient may be random (i.e., the decrease in density is generally not linear or step-like).

[0094] In other embodiments, nanoparticles can be added to the substrate from the first and second surfaces 16, 18. In these embodiments, the surface density or "addition amount" at the first and second surfaces 16, 18 can be substantially equal to each other, or they can be different depending on the application. In these embodiments, the surface density or "addition amount" present in the middle of the substrate is lower than the surface density or "addition amount" at the surfaces 16, 18. For example, the surface density in the middle of the substrate can be about 75% of the surface density at the surfaces 16, 18, or can be about 50%, 40%, or 25%.

[0095] The distribution of nanoparticles across the thickness of the fiber material can be measured, for example, using imaging techniques. An electron microscope or other technique is used to take a magnified view of the fiber product at a horizontal cross section of the product in the middle of the product thickness, which can be compared to an image taken at the upper or lower surface of the product, or all three images can be compared to determine the extent of variation in the amount of deposited nanoparticles. Computer image analysis processing can be employed. For example, in Figure 3 In the present invention, a cross section can be taken at line AA, and a cross section can be taken at line BB. A top view of each cross section can be obtained by an electron microscope, a scanning electron microscope, and other microscopes. For example, a top view of a cross section obtained at section AA can be compared with a top view obtained at section BB. The number of microfibers, the number of nanoparticles, or both in samples of the same two-dimensional size can be evaluated and compared. In addition, imaging techniques can be used on three-dimensional samples. These techniques can be used to evaluate the orientation and other characteristics of the fibers. These techniques can be used to determine that the nanoparticles have been deposited into a certain depth of the substrate, have been substantially deposited in a large part of the substrate, substantially in the entire depth of the substrate, or in a certain depth of the substrate.

[0096] The fibers of the contemplated substrate may be produced by any process including, but not limited to, air laying, spinneret, gel spinning, melt spinning, wet spinning, dry spinning, islands in the sea staple fibers or spunbond, segmented cake staple fibers or spunbond, etc. Such processes have been described in U.S. Pat. Nos. 4,406,950, 6,338,814, 6,616,435, 6,861,142, 7,252,493, 7,300,272, 7,309,430, 7,422,071, 7,431,869, 7,504,348, 7,774,077 9,522,357, 9,993,761 and U.S. Patent Publication Nos. 2009 / 266,759, the entire disclosures of which are hereby incorporated by reference herein for all purposes.

[0097] The cross-section of the contemplated fibers may have a variety of shapes, including but not limited to round, kidney bean, dog bone, trilobal, barbell, bow tie, star, Y, etc. These shapes and / or other conventional shapes may be used with embodiments to achieve desired performance characteristics. The fibers in the substrate are held connected to each other by thermal bonding, chemical bonding, interentanglement, use of a binder (e.g., adhesive), etc.

[0098] The fibers may be man-made or natural. Suitable materials for the fibers include, but are not limited to, polypropylene, polyester (PET), PEN polyester, PCT polyester, polypropylene, PBT polyester, copolyamide, polyethylene, high density polyethylene ("HDPE"), LLDPE, cross-linked polyethylene, polycarbonate, polyacrylate, polyacrylonitrile, polyfumaronitrile, polystyrene, styrene maleic anhydride, polymethylpentene, cyclic olefin copolymers or fluorinated polymers, polytetrafluoroethylene, perfluoroethylene and hexafluoropropylene or copolymers (such as P(VDF-TrFE)) or terpolymers (such as P(VDF-T rFE-CFE)), propylene, polyimide, polyetherketone, cellulose ester, nylon and polyamide, polymethacrylic acid, poly(methyl methacrylate), polyoxymethylene, polysulfonate, acrylic acid, styrenated acrylic acid, pre-oxidized acrylic acid, fluorinated acrylic acid, vinyl acetate, vinyl acrylic acid, ethylene vinyl acetate, styrene-butadiene, ethylene / vinyl chloride, vinyl acetate copolymer, latex, polyester copolymer, carboxylated styrene acrylic or vinyl acetate, epoxy resin, acrylic multipolymer, phenolic resin, polyurethane, cellulose, styrene or any combination thereof. Other conventional fiber materials are contemplated.

[0099] The fibers can include fibers of different sizes, typically having diameters of about 1 to 1000 microns and lengths of about half an inch to three inches. The fibers can be configured as a gradient density media, where the pore size decreases from the upper surface (upstream) to the lower surface (downstream) of the filter to increase capture efficiency and dust holding capacity. This configuration also allows different quantities of nanoparticles to be dispersed into the filter media at different depths. For example, the upstream side of the filter media can have the largest fiber size to allow more void space and a greater density of nanoparticles, while the downstream side of the filter media has smaller sized fibers to provide a lower density of nanoparticles. Alternatively, the structure can be reversed to provide a higher density of nanoparticles in the downstream portion of the filter media.

[0100] The fibers in the media may be held connected to other fibers by thermal bonding, chemical bonding, or entanglement. Bicomponent fibers may be used, particularly in mechanical filtration, and are formed by extruding two polymers from the same spinneret, both polymers being contained in the same filament. Suitable materials for bicomponent fibers include, but are not limited to, polypropylene (PP) / polyethylene (PE), polyethylene terephthalate (PET) / polypropylene (PP), and the like.

[0101] In some embodiments, the substrate may comprise a "high loft" nonwoven material comprising spunbond or through-air bonded carded nonwoven fibers. As used herein, the term "high loft" means that the volume of the void space is greater than the volume of the total solids. In through-air bonded carded nonwoven fibers, the loft of the substrate can be controlled in various ways known to those skilled in the art. For example, the loft can be increased by applying less compressive force to the medium during the bonding process. In another example, a high loft nonwoven material can be produced with fibers having a greater thickness (e.g., a thickness greater than 3 denier, such as 5 denier or greater, 6 denier or greater) (discussed in more detail below). In other embodiments, loft can be increased by using non-concentric biocomponent fibers, such as Figure 5C shown and discussed in more detail below.

[0102] In certain embodiments, the fiber may include a silicon-based coating to improve the efficiency of the filter media in capturing pollutants, particularly pollutants within the E2 and E3 particle groups. The silicon-based coating may include a reactive silicon coarse emulsion. Silicon emulsions may include, for example, dimethyl silicon emulsions, amino-type silicon emulsions, organofunctional silicon emulsions, resin-type silicon emulsions, film-forming silicon emulsions, and the like. In one embodiment, the reactive silicon coarse emulsion comprises amino-functional polydimethylsiloxane and / or polyethylene glycol monotridecyl ether. Suitable silicon coatings are described in commonly assigned U.S. Provisional Patent Application Serial No. 63 / 406,686, filed on September 14, 2022, the full disclosure of which is incorporated herein by reference.

[0103] The filter media may contain a charge additive to modify the triboelectric charge of the fibers and increase the stability and / or duration of the triboelectric charge in the filter. This improves the overall filtration efficiency of the filter without compromising other important properties of the filter, such as life, dust holding capacity, and pressure drop or air flow through the filter. Charge additives suitable for triboelectric charging are described in commonly assigned provisional patent application serial number 63 / 410,731 filed on September 28, 2022, the entire disclosure of which is hereby incorporated by reference herein for all purposes.

[0104] Fiber can have the thickness suitable for application.In some embodiments, at least one dimension of fiber is about 1 to about 10,000 micron or about 1 to about 1,000 micron or about 10 to 100 micron.The thickness of fiber can also be measured with denier, and denier is the measurement unit of fiber linear mass density.In some embodiments, the linear density of fiber can be about 1 denier to about 10 denier.Nanoparticle is at least one dimension is about 1 to about 1,000 nanometer or about 1 to about 100 nanometer fiber.The size of above-mentioned fiber and nanoparticle can be diameter or width, depends on the shape of fiber or nanoparticle.

[0105] For gas filters, such as pleated or non-pleated air filters, the linear density of the fibers can be from about 1 denier to about 10 denier. The filter media can contain fibers having the same or different linear densities.

[0106] The linear density of the fibers in air filters is typically about 3 deniers or less to ensure that the fibers are small enough to capture pollutants passing through the filter. Applicants have unexpectedly discovered that by using nanoparticles dispersed in the filter media, the fibers can have a greater linear density, for example, greater than 3 deniers. This is because the nanoparticles provide significant filtering capabilities. In some cases, the linear density of the fibers can be greater than 3 deniers, 5 deniers or greater, 6 deniers or greater, or as large as 7-10 deniers.

[0107] Applicants have also discovered that in some applications, fibers having a linear density greater than that used in conventional filters (e.g., greater than about 3 denier) provide more open space or pores within the filter media, which allows a greater density of nanoparticles to be dispersed therein. While this may be counter-intuitive to one skilled in the art, Applicants have discovered that incorporating nanoparticles into fibers having a greater linear density actually improves the overall efficiency of the filter.

[0108] In some embodiments, the filter media can include at least two different fiber thicknesses or linear densities to provide at least two different filter layers within the same filter media. For example, in some cases, a portion of the filter media will include fibers with a linear density greater than 3 deniers, for example, 5 deniers or greater or 6 deniers or greater. Another portion of the filter media will contain fibers with a more standard linear density of 3 deniers or less. This double-layer filter media creates a first filter portion and a second filter portion, the first filter portion mainly using nanoparticles with a high density in the fibers of the larger thickness to filter pollutants; the second filter portion mainly uses fibers with a lower linear density to filter pollutants, but both portions can include nanoparticles dispersed throughout the fibers. In some embodiments, the filter media can include three or more separate portions or layers, each with a different range of denier fibers.

[0109] Figure 4A dual-layer filter media is shown, which includes a first substrate 40 having a first surface 42 and a second surface 44 opposite the first surface; and a second substrate 50 having a first surface 52 and a second surface 54 opposite the first surface. The second surface 44 of the substrate 40 is bonded to the second surface 54 of the first substrate in any manner known to those skilled in the art. The first substrate 40 contains fibers 46 with a relatively small linear density, for example, about 3 denier or less. The second substrate 50 contains fibers 56 with a relatively large linear density, for example, about 3 denier or greater, such as 5 denier, 6 denier or greater. The second substrate 50 also includes individual nanoparticles 58 dispersed throughout the fibers 56 and bonded to the fibers 56 and / or retained by the second substrate 50. The first substrate 40 may also include nanoparticles, or may not include nanoparticles.

[0110] The first substrate 40 is configured to filter pollutants primarily using fibers 46, but as previously described, the first substrate 40 may also include nanoparticles. The second substrate 50 is configured to filter pollutants using fibers 56 and nanoparticles 58.

[0111] In some embodiments, the substrate may contain additives, such as antimicrobial and / or antiviral compositions, such as silver, zinc, copper, silicone, tributyltin, organic compounds containing chlorine, bromine or fluorine compounds.

[0112] The fibers may include biocomponent fibers including two or more different fibers bonded to each other. The fibers may include the same material or different materials.

[0113] Figures 5A-5C Various examples of biocomponent fibers that can be used with the fiber materials disclosed herein are shown. Figure 5A A fiber 60 is shown having a core fiber 62 and a surrounding sheath fiber 64. In this embodiment, the core 62 is substantially concentric with the sheath. Figure 5B A biocomponent fiber 70 is shown having first and second fibers 72, 74 arranged side-by-side with one another. Figure 5C A biocomponent fiber 80 is shown having a core fiber 82 and a sheath fiber 84. In this embodiment, the core 82 is non-concentric with respect to the longitudinal axis of the sheath 84, which increases the overall loft of the biocomponent fiber. Of course, other configurations are possible. For example, the core can include shapes other than circular, such as dog-bone, square, triangle, diamond, etc. Alternatively, the fiber can include multiple cores, or it can be divided into three, four, or more quadrants.

[0114] In certain embodiments, the fibrous material (i.e., fiber and / or nanoparticle) can be electrostatically charged so that, for example, pollutants can be captured by mechanical and electrostatic filtration. The bonding between the fiber and the nanoparticle can also be enhanced by electrostatically charging the nanoparticle, the fiber, or both. For example, in certain embodiments, the fiber is electrostatically charged so that mechanical filtration can be achieved by nanoparticles, and electrostatic filtration can be achieved by an electret substrate. Electrostatic or electret substrates can be high-loft triboelectric filtration media made by combing and acupuncture. In one of these embodiments, preferably nanoparticles are deposited in the substrate before acupuncture, and then electrostatic fibers and nanoparticles are acupunctured together.

[0115] The substrate, nanoparticles, or both may be electrostatically charged using triboelectric methods, corona discharge, electrostatic fiber spinning, hydrocharging, charging rods, or other known methods. Corona charging is suitable for charging single polymer fibers or fiber blends or fabrics. Tribocharging can be suitable for charging fibers with different electronegativity. Electrostatic fiber spinning combines the charging of polymers and the spinning of fibers into a one-step process. Charge additives suitable for tribocharging are described in commonly assigned provisional patent application serial number 63 / 410,731 filed on September 28, 2022, the entire disclosure of which is hereby incorporated by reference herein for all purposes.

[0116] Nanoparticles can be selected to have different triboelectric properties relative to the fibers to enhance particle removal using the triboelectric effect. With this approach, the resulting nanoparticles are formed in an electric field and are less susceptible to contamination by chemicals that can mitigate the triboelectric effect. Nanoparticles can also be used with different adsorption properties or surface charge characteristics than the macrofibers, such as for oil or water filtration. This difference can be used to enhance or create local electric field gradients within the filter media to enhance particle removal. The nanoparticles and macrofibers can have different wetting characteristics.

[0117] The fiber material may include a binder or bonding material, such as an adhesive or binder, to promote bonding between fibers and / or retention of nanoparticles in the matrix, so that the nanoparticles can adhere to the fibers or otherwise be retained by the fibers within the matrix to form a stable matrix. The binder or bonding material is preferably present in a relatively small amount to bond a single nanoparticle to the fibers throughout the matrix.

[0118] The adhesive may comprise a variety of conventional materials, including natural based materials such as starch, dextrin, guar gum, etc., or synthetic resins such as EVA, PVA, PVOH, SBR, polyglycolide, etc. In certain embodiments, a solvent based adhesive is used, wherein bonding occurs upon evaporation of the solvent.

[0119] In a preferred embodiment, the adhesive or adhesive material comprises dextrin. In yet another embodiment, the adhesive comprises a composition of various substances (e.g., water, 2-hexyloxyethanol, isopropanolamine, sodium dodecylbenzene sulfonate, lauramine oxide, and ammonium hydroxide). In yet another embodiment, the adhesive comprises at least PVOH. The adhesive can be a solution, emulsion, suspension, hot melt, curable, pure, and / or a combination.

[0120] In some embodiments, adhesive resin is used, and adhesive resin can be cross-linked after adhesive is applied to substrate. Adhesion (water resistance / solvent resistance) can be promoted by self-crosslinking when solvent evaporates in adhesive formulation or heat activation in drying process. For some adhesives, crosslinking can be achieved by electromagnetic radiation (including but not limited to RF, UV or electron beam) of high energy wavelength. The amount of adhesive can be controlled by adjusting the nozzle size of sprayer 140 or the flow rate of control adhesive composition. Adhesive can be applied using nozzle, dip coating or other methods.

[0121] In some embodiments, the adhesive or adhesive material may include a surfactant to reduce the surface or interfacial tension of the adhesive, thereby increasing its dispersibility and wettability, and making it easier for the adhesive to penetrate into a substrate at a certain depth. Suitable surfactants for use with the adhesive disclosed herein include nonionic, anionic, cationic and amphoteric surfactants, such as sodium stearate, 4-(5-dodecyl)benzenesulfonate, sodium dodecylbenzenesulfonate wetting agents, docusate (dioctyl sodium sulfosuccinate), alkyl ether phosphates, benzalkonium chloride (BAC), perfluorooctane sulfonate (PFOS), etc.

[0122] In some embodiments, the substrate includes its own adhesive composition. In these embodiments, the adhesive or adhesive material may or may not be added to the substrate. In one such embodiment, the substrate comprises biocomponent fibers, wherein one of the components comprises an outer sheath at least partially surrounding an inner core (see Figure 5A and 5C ).

[0123] The sheath may comprise a material that bonds to the nanoparticles. For example, the sheath may comprise a material that becomes sticky and / or flows when heated and / or dried. During the heating / drying step (as discussed below), the sheath portion of the fiber is heated to its melting point until it becomes sticky and / or flows to bond the nanoparticles to the substrate. In a preferred embodiment, bonding and drying are performed simultaneously.

[0124] Fig.23A is a magnified image of a fiber product having nanoparticles deposited therein without the use of a binder material. Fig. 23Bis an enlarged image of a fiber product in which a binder material of dextrin and water is used to adhere the nanoparticles to the fibers. As shown, with the use of a binder, the nanoparticles are more uniformly adhered to the fibers.

[0125] exist Fig.23A and 23B In the example of , a substrate having bicomponent microfibers is used, the inner portion of the bicomponent microfibers being polyester and the outer portion being high density polyethylene ("HDPE"). Fig.23A A microfiber fiber product having a bicomponent microfiber substrate is shown, in which a layer of biosoluble glass nanofibers is deposited only on the surface of the substrate, relying on electrostatic forces to retain the nanofibers. Fig.23A Agglomeration of nanofibers can be seen in the substrate, and the retention of nanofibers is poor. The substrate can be produced using meltblowing, spunbonding, or other methods described herein.

[0126] exist Fig. 23B In the example, an adhesive material is used. The substrate is sprayed with a mixture of dextrin and water, and nanoparticles are applied to the substrate, where the uniformity of the nanofibers is higher and the retention rate is greater. In other examples, any adhesive material disclosed herein can be used. In addition, nanoparticles of biosoluble glass have been deposited into a substrate at a certain depth. In this example, the two-component microfiber substrate itself has a MERV rating of 4 to 10, which can be achieved using any method described herein. In one example, due to the deposition of nanoparticles into a substrate at a certain depth and with an electrostatic charge, a microfiber substrate with an initial MERV of 8 has been used to produce a fiber product with a MERV of 13. In another example, a microfiber substrate with an initial MERV of 6 has been used to produce a fiber product with a MERV of 15. The substrate is provided on a roll, and in a roll-to-roll continuous process, the fiber product can be produced on a commercial scale, such as any process and method described herein. In the example, the roll-to-roll process runs at a speed of 30 feet per minute.

[0127] In certain embodiments, the fibrous materials discussed herein can be used as part of a filtration device that captures or absorbs contaminants, such as liquid filters, gas filters for home and commercial air filtration, surgical masks or other face masks, etc. The filtration device can be a mechanical filter, an absorption filter, a barrier filter, an ion exchange filter, a reverse osmosis filter, a surface filter, a depth filter, etc., and can be designed to remove many different types of contaminants from air, water, or other substances.

[0128] In one such embodiment, the fibrous material is incorporated into an air filter that removes particles and pollutants from the air, such as a HEPA filter (i.e., a pleated mechanical air filter), a UV filter, an electrostatic filter, a washable filter, a media filter, a glass fiber filter, a pleated or non-pleated air filter, an activated carbon filter, a bag filter, a V-bank compact filter, a filter sheet, a flat cell filter, a filter cartridge, etc. The fibrous material can comprise the filter media of the air filter and can be supported by a support layer, a scrim layer, or can be included in other layers or materials. Applicants have found that, as discussed herein, incorporating nanoparticles deeply into the fibrous material significantly improves the efficiency of the air filter without compromising other factors, such as the pressure drop (i.e., air flow) through the filter. In addition, these materials increase the overall dust holding capacity, thereby extending the life of the filter, particularly compared to filters that rely only or primarily on electrostatic effects to improve efficiency.

[0129] Traditional home and commercial air filters, such as HEPA filters, are typically rated based on the filter's ability to capture particles ranging from approximately 0.3 to 10 microns. This rating is called the Minimum Efficiency Reporting Value, or MERV, and is established by the American Society of Heating, Refrigerating and Air-Conditioning Engineers (ASHRAE). MERV ratings range from 1-16, with higher values ​​indicating greater efficiency in capturing a particular type of particle. Traditional mechanical air filters typically report a MERV rating of about 8 for the fiber filter material.

[0130] Air filters are usually rated based on their initial efficiency (i.e., the efficiency of the air filter before use) and their efficiency over time and use. The latter efficiency is usually tested through a conditioning procedure, known as Annex J of ASHRAE Standard 52.2.

[0131] The air filters provided herein have an initial MERV rating greater than about 10 and a pressure drop of less than about 0.5 inches of water column. In some cases, the initial MERV rating is about 11 and the pressure drop is equal to or less than about 0.17 inches of water column, or the initial MERV rating is about 13 and the pressure drop is equal to or less than about 0.36 inches of water column, or the initial MERV rating is about 14 and the pressure drop is equal to or less than about 0.5 inches of water column.

[0132] The gas filters provided herein have a MERV rating of 10 or higher after conditioning according to ASHRAE Standard 52.2, Appendix J. In some embodiments, the MERV rating is 13 or higher after conditioning according to ASHRAE Standard 52.2, ISO Standard 16890, or any other acceptable standard in the industry.

[0133] The MERV ratings of the fiber filter media discussed herein will vary based on many factors, including the type and size of fibers used in the filter media, the density of individual nanoparticles within the filter media, the width of the filter media, the number and size of pleats (if any), etc. MERV ratings can be measured for sheets of fiber products as well as fiber products formed into pleated filter media, and the pressure drop for each product can be different. Likewise, the pressure drop across the filter media will also depend on many factors, including those described above.

[0134] One factor that affects the MERV rating and pressure drop is the density or amount of the nanoparticles in the substrate relative to the density of the fibers in the substrate. Applicants have found that the lower the ratio between the substrate density and the nanoparticle density, the higher the MERV rating of the filter and the higher the pressure drop. In certain embodiments, the nanoparticle surface density of the filter media described herein is about 0.1 g / m 2 About 20 g / m 2 , preferably at least about 2 g / m 2 .

[0135] In some cases, the density of the nanoparticles will also depend on the density of the actual filter media (i.e., the density of the coarse fibers). As discussed in more detail below with reference to Table 2 below, a density ratio of about 67 (substrate gsm divided by added nanoparticle gsm) results in a pressure drop of about 0.14 inches of water column and an initial MERV rating of 10. A density ratio of about 33.4 increases the MERV rating to 10, but only results in a pressure drop of about 0.17. A density ratio of about 22.3 increases the initial MERV rating to about 12 with a pressure drop of about 0.24 inches of water column.

[0136] Thus, the efficiency or MERV rating of the filter can be increased as the amount of nanoparticles added increases. In particular, the applicant has found that, for example, an addition amount of at least 2 g / m 2 A filter with a MERV rating of approximately 10 can be achieved. 4 or 6 g / m 2 The addition of 10 g / m 2 Addition levels of 1% or more produce filters with a MERV rating of 15 or higher.

[0137] Applicants have also discovered that including fibers with greater thickness or linear density results in larger pore sizes, and therefore greater pore volumes, thereby achieving a higher density of nanoparticles within the substrate. This results in higher MERV ratings and pressure drops (as discussed below with reference to Table 2). For example, Applicants have been able to produce air filters with a MERV rating of 14 and a pressure drop of 0.5 inches of water column using 5 denier biocomponent fibers. Similarly, Applicants were able to produce filters with a MERV rating of 13 and a pressure drop of only about 0.29 inches of water column using 5 denier biocomponent fibers.

[0138] Figure 6 An example of a pleated filter media 90 is shown in FIG. Depending on the application, the filter 90 may include about 0 to 10 pleats per inch. The filter media may be mounted in a cardboard or metal frame and used as an easily replaceable filter product ( Figure 7 ). As shown, a gas filter 94 is produced using the fibrous materials described herein. As shown, the filter 94 includes a pleated fiber filter medium 96 and a support layer 98 that provides rigidity and structure to the filter medium 96.

[0139] Fig.11 A gas filter 109 produced using the fibrous material described herein is shown. The gas filter 109 includes a fibrous substrate having fibers and nanoparticles dispersed in the substrate at a certain depth. The substrate is then rolled into a cylinder, cone, or other suitable shape and can be used in applications such as gas turbine and compressor intake filters, panel filters, etc.

[0140] Other types of filters that can be developed using the fiber materials disclosed herein include conical filter cartridges, square end cap filter cartridges, bag filters, V-bank compact filters, plate filters, flat cell filters, pleated or non-pleated bag filter cartridges, and the like.

[0141] The fiber products disclosed herein can be used in medical masks or other medical applications, such as filter cartridges in respirators. Medical masks are intended to protect medical staff and / or patients from microorganisms and other substances. For example, medical masks can block bacteria (e.g., which can be about 3 microns in size) and viruses (e.g., which can be about 0.1 microns in size). The mask is made of multiple layers of fiber material and has ear loops, laces or other structures for attaching the mask to the face of a person. Metal wire can be incorporated into at least the upper part of the mask so that at least this part fits the face of a person. The mask can include a rigid polymer structure for fixing the multiple layers of fiber material in front of the face of a person. In one example, the mask has three layers. The outer layer and the inner layer contain a fiber material (e.g., spunbond polypropylene) that provides air permeability, but any material mentioned herein can also be used. The middle layer is located between the inner layer and the outer layer and contains a microfiber substrate having nanoparticles deposited into the substrate at a certain depth to provide an initial MERV greater than 8, preferably a MERV greater than 10, and more preferably a MERV of 13 or greater. The pressure drop through the mask is 3 to 6 mm H2O, more preferably 4 mm H2O for breathability. The mask is expected to have an efficiency of about 95%. Other examples of masks have four or more layers. Multiple layers of fiber products can be combined into a single mask.

[0142] In certain embodiments, the fibrous material may be included in a film or layer that includes holes, pores, or perforations. The holes may be embossed into a pattern (e.g., circles, diamonds, hexagons, rectangles, triangles, rectangles, etc.) and then stretched until holes are formed in the thinned areas produced by the embossing. Such an open-cell substrate may be formed from a variety of polymers (e.g., polypropylene, polyethylene, high-density polyethylene ("HDPE"), etc.). The polymer layer may, for example, comprise an extruded film. Open-cell films are commercially available and are available as The substrate is provided in the form of a roll and the nanofibers are deposited into the substrate in a roll-to-roll process. Figures 10A-10E Examples of apertured films formed using the methods described herein are shown.

[0143] In other embodiments, the gas filter comprises a filter medium and a substantially rigid support layer bonded to the filter medium. The support layer includes fibers and individual nanoparticles dispersed at a depth within the layer. The nanoparticles are configured to filter pollutants that pass through the support layer.

[0144] refer to Figure 8 , the composite filter member 814 includes an internal filter substrate 812 and one or more filter support members or membrane layers 810. The support member 810 can be formed by an extruded sheet of a polymer, such as a polypropylene film, a high-density polyethylene film, a polylactic acid film, or a thermoplastic polymer material, such as an extrudable fluoroplastic material, in an embodiment, a perfluoroalkoxyalkane (PFA) copolymer made from comonomers polytetrafluoroethylene and perfluoroalkyl vinyl ether. However, other polymer materials can be used, such as fluoroplastics, such as ethylene trifluorochloroethylene (ECTFE), ethylene tetrafluoroethylene (ETFE), or polyvinylidene fluoride (PVDF).

[0145] In certain embodiments, the support membrane layer 810 comprises individual nanoparticles dispersed at a depth within the membrane layer 810, as described above. The nanoparticles allow the support membrane layer to filter at least some contaminants that pass through the filter membrane layer 814, i.e., in addition to the filtration provided by the internal filter substrate 812. In other embodiments, the filter substrate 812 and / or the support membrane layer 810 include such nanoparticles.

[0146] Fluoroplastic materials such as PFA are well suited for use in filters for cleaning semiconductor components and other environments where extremely high cleanliness is required and the potential for contamination is minimized. Such support membrane layers are designed to direct fluids along their surfaces and also to direct fluids through the structure to the underlying filter substrate to remove unwanted particles from the filtrate.

[0147] like Fig. 9A and 9BAs shown, the support film layer 810 may include a plurality of holes 828. The shape of the holes is preferably circular, but it will be appreciated that other shapes are also possible, such as square, rectangular, triangular, etc. The substrate may be wound into a roll, then unwound and directed through a punching machine to form the desired predetermined pattern of holes 828 in the Z direction ( Fig. 9A ). Optionally, after being set up, the sheet can be directed through a punch press in a continuous operation to form a predetermined pattern of holes 828 therein.

[0148] refer to Fig. 9B After opening the pores, the filter support member can be stretched in the machine direction, as shown by double-headed arrow 940, to elongate the pores 828 to provide a larger open area for the passage of the fluid to be filtered by the filter media or substrate 812.

[0149] In an optional embodiment, the support membrane layer 810 can be porous (i.e., not having pores 828, or in addition to having pores 828). In this embodiment, additional fluid flow can be achieved through a substantially porous support membrane layer. In an exemplary embodiment, the porosity value of the support membrane layer is at least 0.5 or 50%, preferably at least 0.8 or 80%, and more preferably about 0.86 or 86%. The porosity value is defined as the non-solid or pore volume fraction of the total volume of the material. A more complete description of this composite filter medium can be found in PCT Application Serial No. US2020 / 040941, the complete disclosure of which is incorporated herein by reference in its entirety for all purposes.

[0150] The support membrane layer of the present filter can be prepared by any method known to those skilled in the art. Fig. 9A and 9B In one example shown, the support film layer includes ribs. For example, the support film layer can be made by extruding a polymer material to form a sheet and then passing the sheet through a nip area provided by opposing rollers; at least one roller has an outer surface with countersunk grooves. The countersunk grooves in one roller are aligned with the outer surface or countersunk grooves of the other roller in the nip area to form a ribbed sheet having ribs upstanding from at least one surface of the sheet. Optionally, the ribs can be formed in an extrusion process or a known embossing method. Once the ribs are formed, the support film layer can be wound into a roll, subsequently unwound and directed through a press to form a desired predetermined pattern of holes in the Z direction thereof. Optionally, after setting, the support film layer can be directed through a punch press in a continuous operation to form a predetermined pattern of holes therein, such as Fig. 9A Optionally, the support film layer can be stretched in the machine direction ( Fig. 9B The pores are elongated to provide a larger open area for the passage of a fluid to be filtered through, for example, a filter layer or a substrate.

[0151] Fig.12 The overall system 110 for producing the above-mentioned fiber materials and other products is schematically depicted. As shown, the system 110 includes a feeder 120 for advancing a substrate 130 of fiber or other material during the production process. The system 100 also includes a coater 140, a fiberizing system 150, and a heating and / or drying device 160. In certain embodiments, the system 100 also includes a vacuum or other negative pressure source 170 located below the substrate 130, which is opposite to the fiberizing system 150.

[0152] In one embodiment, the feeder 120 includes a winder 122 at the downstream end of the process and an unwinder 124 at the upstream end, which continuously winds the substrate 130 through the system 100. In certain embodiments, the feeder 120 may also include a support surface (not shown) extending between the winders for supporting the substrate 130 as it moves downstream through the system 100. In other embodiments, the substrate is unwound directly from the unwinder 124 to the winder 122 without another support surface.

[0153] The coater 140 is configured to spray droplets of an adhesive or bonding material (e.g., an adhesive or binder) onto the substrate 130 so that the nanoparticles can adhere to the fibers within the substrate 130 to form a stable matrix. The adhesive is preferably present in a relatively small amount to bond individual nanoparticles to the fibers throughout the substrate 130. In a preferred embodiment, the coater 140 includes a nozzle sized to generate adhesive droplets having a diameter of about 20 to 30 microns to increase the penetration depth of the adhesive through the substrate 130. Of course, droplet size may be affected by many other parameters, including air pressure, air volume, air temperature, humidity, spray horn design, rheology / viscosity of the adhesive, carrier, etc.

[0154] Of course, it should be recognized that coating the substrate with the adhesive or bonding material can be achieved by other coating methods including ultrasonic spraying, dip coating, spin coating, gravure coating, kiss roll coating, screen coating, powder coating, electrostatic, sputtering or similar coating techniques.

[0155] As described above, the adhesive may include various conventional materials, including natural based materials such as starch, dextrin, guar gum, etc., or synthetic resins such as EVA, PVA, PVOH, SBR, etc. In certain embodiments, a solvent based adhesive is used, wherein bonding occurs when the solvent evaporates.

[0156] In a preferred embodiment, the adhesive comprises dextrin. In another embodiment, the adhesive comprises a composition of various substances (e.g., water, 2-hexyloxyethanol, isopropanolamine, sodium dodecylbenzene sulfonate, lauramine oxide, and ammonium hydroxide). In another embodiment, the adhesive comprises PVOH. The adhesive can be a solution, emulsion, suspension, hot melt, curable, pure, and / or a combination.

[0157] In some embodiments, an adhesive resin is used, and the adhesive resin can be cross-linked after the adhesive is applied to the substrate 130. Adhesion (water resistance / solvent resistance) can be promoted by self-crosslinking when the solvent in the adhesive formulation evaporates or thermal activation during drying. For some adhesives, crosslinking can be achieved by electromagnetic radiation of high energy wavelengths (including but not limited to RF, UV or electron beams). The amount of the adhesive can be controlled by adjusting the nozzle size of the sprayer 140 or controlling the flow rate of the adhesive composition.

[0158] In some embodiments, the adhesive can include a surfactant to reduce the surface or interfacial tension of the adhesive, thereby increasing its dispersibility and wettability, and making it easier for the adhesive to penetrate into a substrate at a certain depth. Suitable surfactants for use with the adhesive disclosed herein include nonionic, anionic, cationic and amphoteric surfactants, such as sodium stearate, 4-(5-dodecyl)benzenesulfonate, sodium dodecylbenzenesulfonate wetting agents, docusate (dioctyl sodium sulfosuccinate), alkyl ether phosphates, benzalkonium chloride (BAC), perfluorooctane sulfonate (PFOS), etc.

[0159] In some embodiments, sprayer 140 is located upstream of fiberizing system 150 to spray the binder before depositing the nanoparticles. In other embodiments, sprayer 140 is located downstream of fiberizing system 150 to spray the binder after depositing the nanoparticles. In other embodiments, system 100 includes two spray layers; one located upstream of fiberizing system 150, and a second sprayer (not shown) located downstream of fiberizing system 150 to coat substrate 130 with a second binder after depositing the nanoparticles.

[0160] In some embodiments, each sprayer 140 has more than one nozzle head. For example, the nozzle heads can be arranged in series to obtain better uniformity or increase the fiber spray width. Alternatively, the nozzle heads can be placed in parallel (i.e., across the width of the substrate) to ensure that the adhesive is applied to the entire width of the substrate.

[0161] In a preferred embodiment, a negative pressure source or vacuum source (not shown) is arranged below the substrate 130, opposite to the sprayer 140, to increase the penetration depth and uniformity of the adhesive. The negative pressure source can be any suitable suction device that draws the adhesive through the substrate, such as a suction pump, etc.

[0162] In some embodiments, the substrate includes its own binder composition. In these embodiments, the binder may or may not be added to the substrate. In one such embodiment, the substrate comprises biocomponent fibers 600, wherein one of the components comprises an outer sheath 64 at least partially surrounding an inner core 62. In certain embodiments, the sheath 64 and the core 62 may be substantially concentric with each other ( Figure 5A In other embodiments, the core 84 may be non-concentric with the sheath 82 ( Figure 5C In other embodiments, the core 72 and the sheath 74 may be placed side by side with each other ( Figure 5B ). Of course, other configurations are also possible. For example, the core 184 can include shapes other than circular, such as dog-bone, square, triangle, diamond, etc. Optionally, the fiber 180 can include multiple cores, or it can be divided into three, four or more quadrants.

[0163] The sheath 64 may include a material that bonds to the nanoparticles. For example, the sheath 64 may include a material that becomes sticky and / or flows when heated and / or dried. During the heating / drying step, the sheath 64 portion of the fiber is heated to its melting point until it becomes sticky and / or flows to bond the nanoparticles to the substrate. In a preferred embodiment, bonding and drying are performed simultaneously in the drying device 160.

[0164] Fig.13 Schematically depicted is a fiberizing system 150 for converting a group of nanofibers into individual nanoparticles. As used herein, the term "fiberizing" means converting (e.g., opening, separating, isolating and / or individualizing) clusters, clumps, or other groups of nanoparticles that may or may not be entangled with one another into individual nanoparticles having at least one dimension less than 1 micron. Figures 14A-14C shows large clusters of entangled nanofibers ( Fig.14A ), small clusters of tangled nanofibers ( Fig. 14B ) and single nanoparticles ( Fig. 14C ) instance.

[0165] As shown, the fiberizing system 150 includes a feeder 200, such as a hopper, for feeding relatively large or large clusters / agglomerates of nanoparticles (see Fig.14A) is introduced into the system 150. The feeder 200 may comprise any suitable hopper device known to those skilled in the art, and is preferably configured to introduce large particle clusters into the process at a specified rate, which rate depends on the fiberization rate downstream. The nanoparticles may be introduced continuously at a specified rate, or at intervals of a specific rate. The bundled large clusters of nanoparticles may be broken up before being introduced into the feeder 200.

[0166] It should be appreciated that the nanoparticles can be introduced into the fiberizing device 150 in a variety of different forms. For example, raw nanofibers can be produced as long separate fibers. In this form, the nanofibers can be cut to obtain a desired length to diameter ratio.

[0167] The system 150 also includes a separator 210, such as a blender, for separating or decomposing large clusters / agglomerates of nanoparticles into small clusters / agglomerates of nanoparticles (see Fig. 14B ). The feeder 200 delivers the nanofibers to the separator 210 in a stable and continuous state by any mechanical means. The delivery speed will depend on various factors, such as the speed of the substrate 130 along the feeder 120, the fiberization rate of the nanoparticles, etc. By controlling the amount of nanoparticles falling into the separator 210, the amount of nanoparticles dispersed into the substrate can be controlled, thereby achieving a continuous production process.

[0168] In one embodiment, the separator 210 includes a housing 212 having a first opening 214 coupled to the feeder 200 and a second opening 216 coupled to the downstream process. The size of the second opening 216 is preferably such that only nanofiber clusters of a certain size can pass through. The separator 210 may include a plurality of rotatable blades (not shown) designed to rotate about a vertical axis within the housing 212 to separate and open the coarse nanofiber clusters. The blades may have the same or different pitches and cambers to allow the entangled fibers to be sequentially decomposed or "opened" when moving from the first opening 214 to the second opening 216.

[0169] The fiberizing system 150 also includes an airflow (discussed in more detail below) throughout the system extending from the separator 210 to the nozzle 220. The airflow (along with a series of pumps discussed below) provides the motive force to move the nanofibers through the system 150. In one embodiment, the airflow is generated by an air compressor 230 configured to supply compressed air to the system, but it will be appreciated that other forms of gas may be used to convey the nanofibers through the system 150.

[0170] The system 150 includes one or more pumps for moving the nanofiber clusters and ultimately individual nanoparticles throughout the system. The pump may include any suitable pump, such as a positive displacement pump, a centrifugal pump, an axial flow pump, etc. In one embodiment, the first pump 240 includes a first inlet fluidly coupled to the air compressor 230 through a first channel 242 and a second inlet fluidly coupled to the separator 210 through a second channel 244. Compressed air is sucked into the first pump 240, which generates a negative pressure (e.g., a vacuum) to draw the nanofiber clusters from the separator 210 into the pump (discussed in more detail below). The system 150 may also include a second and third pumps 250, 260, each of which is fluidly coupled to the outlet of the first pump 240. Similarly, the second and third pumps 250, 260 generate a negative pressure to pull the nanofiber clusters through the third channel 252.

[0171] In certain embodiments, the pump 240 includes an ejector 300. Fig.15 As shown, the ejectors 300 each include a motive fluid inlet 302 and a nanofiber inlet 304, which are coupled to an outlet 306 through a fluid channel 308. The fluid channel 308 includes a converging inlet nozzle 310, a diffuser throat 312, and a diverging outlet diffuser 314. High-pressure, low-speed air is converted into low-pressure, high-speed air, thereby generating the pressure difference required for suction. Based on the Venturi effect and the Bernoulli principle, the primary fluid medium (e.g., compressed air) is used to generate a vacuum to draw the nanofibers into the ejector 300 and discharge them through the outlet 306. The diameter of the ejector 300 depends on the volume flow rate of the compressed air, the suction requirements, the pressure drop, and the fluid pressure of the compressed air.

[0172] review Fig.13 , the third channel 252 includes a joint 254 that divides the third channel 252 into two independent channels, each of which leads to the second and third pumps 250, 260. The joint 254 preferably includes a surface or wall substantially perpendicular to the third channel 252 to form a T-shaped intersection. The surface can be any surface that hinders the nanofibers from flowing through the channel, such as the inner wall of the channel at the connection point, or other inner walls with changes in direction, such as curved surfaces, vertical surfaces, etc. Optionally, the channel may include walls or other surfaces arranged in the channel or protruding into the channel in the fluid path. In one embodiment, the channel extends to a roughly T-shaped joint that includes two independent channels extending from the joint. The second ejector is configured to pull the nanofibers into the T-joint at a speed sufficient to break up at least some of the nanofibers.

[0173] As the nanofiber clusters move through the third channel 252, they are pushed toward the surface or wall due to the negative pressure applied by the second and third pumps 250, 260. The velocity of the nanofibers relative to the joint 254 creates collisions with sufficient kinetic energy to cause at least some of the nanofiber clusters to break up into smaller nanofiber clusters and / or into individual nanoparticles having at least one size less than 1 micron.

[0174] To generate the kinetic energy required to break up the nanofiber clusters, air is propelled throughout the system 150 at a rate of about 500 feet per minute (fpm) to about 10,000 feet per minute, preferably about 2,000 fpm to about 6,000 fpm. The system 150 includes a sufficient amount of suction pressure, preferably at least about 20 psi. The suction pressure generates a total pressure of at least about 100 psi throughout the system.

[0175] In certain embodiments, the system 150 further includes fourth and fifth fluid channels 262, 264, which couple the outlets of the second and third pumps 250, 260 to the reactor 270. Fig.16 As shown, the reactor 270 includes a top surface 272, a bottom surface 274 and an inner annular chamber 276 extending from the top surface 272 to the bottom surface 274. The reactor 270 also includes a central tube 275 having an open upper inlet 278 and an outlet 280. The reactor 270 may also include one or more upper outlets 282. The reactor 270 may be coupled to an energy source (not shown) that is configured to generate a vortex of vortex gas in the annular chamber 276. The energy source may include any suitable energy source, such as a pump, a compressor, a generator, etc. The vortex gas preferably flows from the bottom of the reactor 270 around the central tube 275 to the top, so that the nanofiber clusters and individual nanoparticles move upward from the bottom surface 275 to the top surface 272.

[0176] In another embodiment, the generation of vortex does not require a separate energy source. In this embodiment, nanofiber clusters 290 and individual nanoparticles 292 enter the reactor 270 through bottom inlets 284, 285, 286, 287. The inlets 284, 285, 286, 287 are tilted upward to facilitate the movement of nanofibers and nanoparticles around the central tube 275. In a preferred embodiment, at least one or more of the inlets 284, 285, 286, 287 are tilted so that the nanofibers and nanoparticles are substantially tangential to the central tube 275 when entering the reactor 270. Once they enter the annular chamber 276, the velocity vectors (speed and direction) of the nanofibers and nanoparticles generate vortices within the reactor 270, causing them to swirl around the central tube 275 and reach the upper part of the chamber 276. The swirling gas preferably flows from the bottom of the reactor 270 around the central tube 275 to the top so that the nanofiber clusters and individual nanoparticles move upward from the bottom surface 275 to the top surface 272. The nanofibers 290 and nanoparticles 292 are blown from the bottom of the reactor to the top without any interference. The vortex in the chamber 276 can further break up (eg, open, separate and / or individualize) the nanofiber clusters 290 as they pass through the reactor 270.

[0177] In some embodiments, the reactor 270 may also be coupled to an energy source (not shown) configured to generate a vortex of swirling gas within the annular chamber 276. The energy source may include any suitable energy source, such as a pump, a compressor, a generator, and the like.

[0178] The system 100 may also include another pump or negative pressure source coupled to the upper outlet 282 (e.g., see Fig.17 ). The negative pressure draws the fibers out of the outlet 282, so that the fibers 290 leave the reactor 270. Since the individual nanoparticles 292 are significantly lighter than the tangled nanofibers 290 that are still gathered together, these individual nanoparticles 292 are sucked into the upper inlet 278 of the central tube 275. At the same time, the larger and heavier nanofiber clusters 290 that have not yet been decomposed are drawn out from the upper outlet 284. The upper outlet 284 can be coupled to other pumps (not shown), or to the first pump 240. In this way, the nanofiber clusters 290 are sent back into the process for further decomposition, thereby forming a re-feed system to further decompose the remaining nanofiber clusters.

[0179] The outlet 280 of the central tube 275 is coupled to the nozzle 220 (see Fig.13). Individual nanoparticles 292 are drawn into nozzle 220 where they are dispersed onto the substrate surface or into the fiber stream (discussed below). Nozzle 220 may comprise any suitable nozzle known to those skilled in the art. In one embodiment, nozzle 220 has a plurality of outlets whose outer dimensions are tailored to the size (i.e., area) of the substrate passing under nozzle 220. Nozzle 220 will disperse the nanoparticles onto the substrate at a rate driven by the pressure of the entire system.

[0180] In certain embodiments, system 100 includes more than one nozzle coupled to outlet 280 of reactor 270. The nozzles can be arranged on the substrate in any suitable arrangement (eg, side-by-side, in series, in parallel, etc.).

[0181] It will be appreciated that pump 240 or pumps 250, 260 can feed the nanofiber / air mixture stream directly into nozzle 220 (i.e., bypassing reactor 270). In this embodiment, the pressure within the system is designed to generate sufficient kinetic energy to break up or open up substantially all of the nanofibers into individual nanoparticles, thereby eliminating the need for reactor 270 to separate the nanoparticles from larger fiber clusters.

[0182] Reference Fig.17 , another embodiment of a fiberizing system 320 will now be described. As shown, the fiberizing system 320 includes a separator 325 for separating larger or large nanofiber clusters passing through the system 320 into smaller nanofiber clusters. A first ejector 326 is coupled to the outlet of the separator 325 for drawing the nanofibers from the separator 325 into the system 320. An air compressor (not shown) is also coupled to the ejector 326 to provide a motive fluid, as described above.

[0183] Similar to the previous embodiments, the second and third ejectors 330, 340 are coupled to the outlet of the first ejector 326. The nanofibers are drawn from the first ejector 320 and are pushed toward the surface of the T-junction 350 to break up at least some of the nanofibers into smaller clusters or individual nanoparticles.

[0184] Each of the second and third ejectors 330, 340 has an outlet coupled to another T-junction 360, 370. As before, the nanofibers are pushed toward the surface of the T-junction 360, 370 to further decompose them. The T-junction 360, 370 are each coupled to two fluid channels entering the bottom 380 of the reactor. Thus, the bottom 380 of the reactor has four separate inlets 382, ​​384, 386, 388 for the passage of the nanofibers. Each of these inlets is preferably tilted upward and located at opposite corners of the reactor. This allows the nanofibers to enter the vortex of the reactor and then swirl upward to the upper portion 390 of the reactor.

[0185] As previously referenced Fig.16 The reactor comprises an annular chamber, wherein the central tube has an open upper end and a lower end coupled to a nozzle. The nanofibers that have been fully decomposed into individual nanoparticles flow through the open upper end and enter the central tube for dispersion through the nozzle. The heavier nanoparticle clusters that have not yet decomposed leave the reactor through one of four independent outlets 392, 394, 396, 398. Ejectors 410, 420 provide the power to extract the nanofibers from the reactor 400, as described above. The outlets 392, 394 are each coupled to the ejector 410 by a T-shaped intersection 412, and the outlets 396, 398 are each coupled to the ejector 420 by a T-shaped intersection 422. In this case, the nanofibers flow into one channel from two channels when passing through the intersections 412, 422.

[0186] The ejectors 410, 420 are each coupled to the T-junctions 430, 440. As previously described, the nanofibers are pushed into the T-junctions 430, 440 to further break them down into individual nanoparticles. Then, the T-junctions 430, 440 are each coupled to the bottom 380 of the reactor 400 (via inlets 432, 434, 442, 444). This allows the nanofibers to return to the reactor 400 for further processing. This process is continued for each nanofiber cluster until it is completely broken down into nanoparticles and enters the nozzle through the central tube. As a final step, the individualized nanofibers are sprayed from the nozzle onto any substrate or mixed with any fiber spinning stream. In this process, the suction is up to 20psi and the pressure is up to 100psi.

[0187] In certain embodiments, fibrosis system 150 may include a separate control system that monitors nanofibers to determine when they are broken down into individual nanoparticles suitable for passing through nozzles. The control system may, for example, simply monitor the pressure of the entire system to ensure that nanofibers are subjected to enough pressure to be broken down into nanoparticles. Alternatively, the control system may include various sensors arranged by the system to detect the characteristics of nanoparticles, such as weight or size. The sensor may be arranged in, for example, reactor 400 so that the control system may control the various parameters of reactor 400, such as the negative pressure applied to outlet 392,394,396,398, the speed of the eddy current of the annular chamber, or the pressure applied to the center tube that nanoparticles are sucked into the nozzle.

[0188] Fig.18Another embodiment of a system 500 for producing a multilayer fibrous material is shown. As shown, the system 500 includes first and second unwinders 502, 504 and a single winder 506 for winding first and second substrates 510, 512 downstream of the system 500. As with the previous embodiments, the system 500 may also include a support surface (not shown) for each substrate 510, 512. The first and second unwinders 502, 504 are used to advance the first and second substrates 510, 512 into the process, where they are connected together and then wound onto the single winder 506, as described below.

[0189] The system 500 includes first and second spray guns 520, 522, respectively, located downstream of the first and second unwinders 502, 504, for applying adhesive to the first and second substrates 510, 512. The system 500 also includes first and second fiberizing systems / devices 530, 532, which are located downstream of each spray gun 520, 522. As previously discussed, the fiberizing devices 530, 532 generate individual nanoparticles and disperse the nanoparticles onto the substrates 510, 512.

[0190] After the nanoparticles are dispersed into the substrates 510, 512, the two substrates are connected together at the connection point 540 so that they are advanced downstream together. The two substrates may be bonded to each other at this point, or they may simply be placed one on top of the other.

[0191] The system 500 also includes a heater / drying device, such as an IR oven 550, located downstream of the connection point 540 of the two substrates. The heating / drying device heats and dries the two substrates to bond them to each other and to bond the nanoparticles to the fibers within the substrates. The substrates can, for example, be laminated to each other.

[0192] In certain embodiments, nanoparticles are dispersed in two substrates 510, 512. In such an embodiment, system 500 is designed so that nanoparticles are dispersed by the first surface of each substrate. Then, substrates can be connected together so that the first surface faces each other. Alternatively, the first surface can be opposite to each other (that is, substrate is connected at the second relative surface of each substrate). In another embodiment again, the first surface of the first substrate is connected to the second surface of the second substrate.

[0193] Fig.19A filtration product 700 is shown, comprising a filter medium 710 of a fibrous material, including fibers 722 and nanoparticles 720 dispersed in at least a portion of the filter medium 710. As shown, the filter medium 710 has a first upper surface 712 and a second lower surface 714. The nanoparticles have been dispersed through the upper surface 712 so that they extend beyond the upper surface 712 and into the filter medium 710 to a certain depth, as described above. The filtration product 700 also includes a support layer 730, which can be any suitable support layer known in the art, such as a substantially rigid polymer that provides support for the filter medium 710, or an open membrane having a plurality of pores for gas or fluid to pass through (as described above).

[0194] Fig. 20 Another filtration product 740 is shown that includes a filter media 710 of fibrous material including fibers 722 and nanoparticles 720 dispersed in a portion of the filter media 710. In this embodiment, the product 740 includes a scrim layer 750 bonded to a support layer 730.

[0195] Fig.21 A dual layer filtration product 760 is shown, which includes first and second filter media 762, 764 bonded to each other. As shown, nanoparticles 720 have been dispersed in a certain depth of each filter medium 762, 764. In this embodiment, the nanoparticles 720 have been dispersed through the inner surface 766, 768 of the filter media 762, 764. In another embodiment (not shown), the nanoparticles are dispersed through the outer surface 770, 772 of the filter media 762, 764. In yet another embodiment, the nanoparticles 720 can be deposited on the inner surface 766 of the medium 762 and the outer surface 772 of the medium 764.

[0196] In yet another aspect, the system for making fibrous material comprises the first device for generating one or more fiber streams and the second device for isolating nanoparticles in the gaseous medium.The second device is dispersed into the nanoparticles in the stream and the stream is fed into the fiber stream to form the fibrous material.The system may also include a dispersing device, for example a nozzle, which is coupled to the second device and is configured to feed the nanoparticles substantially uniformly into the fiber stream.Fiber stream can be generated with any suitable mechanism known in the art (for example melt-blown, spunbond or spunlace, thermal bonding, combing, air-laid, wet-laid, extruded, co-molded, acupuncture, stitching, hydraulic entanglement, etc.).

[0197] In one example, the system can include a spunbond line, in which filaments are formed by spinning molten polymer and stretching the molten filaments. The fiber bundles of the filaments are separated and spread, and then layered on a net to form a web. The fibers are bonded in the form of sheets by thermal bonding and embossing. The first stream 630 can be introduced, for example, before the attenuation zone or before the bonding (consolidation) process.

[0198] In another embodiment, the system can include two carding machines arranged in series with each other. The first stream 630 can be introduced at any point after the first carding line and before the second carding line, so that the nanoparticles are sandwiched between the two carded fiber webs. Afterwards, all fibers (including the nanoparticles) are bonded together in a hot air bonding oven (the nanoparticles are thermally interlocked).

[0199] Fig. 22 Another embodiment for generating one or more fiber streams is shown. In this embodiment, nanoparticles are dispersed between two meltblowing dies where molten polymer is pushed through small holes to make fibers. When the nanoparticles encounter the fibers while they are still sticky, they mechanically entangle with the fibers and thermally bond to the fibers. Therefore, in some embodiments, no additional bonding process is required.

[0200] like Fig. 22 As shown, the apparatus 600 for forming a fibrous structure comprises a fiberizing system 610 similar to one of the systems and devices described above. The fiberizing system 610 comprises a nozzle 620 or similar device for dispersing individual nanoparticles into a first stream 630. The apparatus 600 also comprises a system for generating one or more fiber streams that will be combined with the single nanoparticle stream 630. The system may comprise any system known in the art, such as spunbonding, carding, extrusion, etc.

[0201] In another embodiment, the equipment includes first and second feeders, such as hoppers 640, 642, which are coupled to first and second extruders 650, 652. For example, each extruder can include an extrusion screw (not shown) driven by a conventional drive motor (not shown). When polymer is advanced through extruders 650, 652, polymer is gradually heated to a molten state due to the drive motor rotating the extrusion screw. Thermoplastic polymers are heated to a molten state and can be completed in multiple discrete steps, when they advance to two melt-blown dies 660, 662 through discrete heating zones of extruders 650, 652 respectively, their temperature gradually increases. Melt-blown dies 660, 662 can be another heating zone, in which the temperature of the thermoplastic resin is maintained at a higher level to extrude.

[0202] Each meltblowing die 660, 662 is configured so that the two attenuating air streams of each die converge to form a single air stream that entrains and attenuates the molten strands as they flow from the small holes or orifices 672 in the meltblowing die. The molten strands 20 are attenuated into fibers or, depending on the degree of attenuation, into microfibers, which have a relatively small diameter, typically smaller than the diameter of the orifices 672. Thus, each meltblowing die 660, 662 has a corresponding single primary air stream 680, 690 containing entrained and attenuated polymer fibers.

[0203] The main gas streams 680, 690 containing polymer fibers are aligned to converge at the forming zone 700. In addition, a first stream 630 of individual nanoparticles is added to the two main gas streams 680, 690 of thermoplastic polymer fibers or microfibers at the forming zone 30. The introduction of the individual nanoparticles into the two main gas streams 680, 690 of fibers is intended to produce a distribution of secondary fibrous materials 32 in the combined main gas streams 680, 690 of fibers. This can be achieved by merging the first stream 630 of individual nanofibers between the two main gas streams 680, 690 so that all three gas streams converge in a controlled manner.

[0204] Examples of suitable meltblowing dies that can be used to produce nonwoven materials are discussed in more detail in U.S. Patent Nos. 6,972,104, 8017534, and 7772456, and U.S. Patent Application No. US20200216979A1, the complete disclosures of which are incorporated herein by reference in their entirety for all purposes.

[0205] Example 1

[0206] A microfiber substrate of bicomponent fibers having an inner circular portion of polyester and an outer concentric portion of HDPE is provided in the form of a roll. In a roll-to-roll process, the substrate is sprayed with an adhesive and nanofibers or nanoparticles of biosoluble glass fibers are deposited. The nonwoven product is then heated in an oven and the cooled nonwoven product is collected onto another roll.

[0207] Nanoparticles are based on the following Figure 12-16 The process described in was deposited. In the experiments, biosoluble glass nanofibers were used. The nanofiber diameter was about 700 nanometers and the length was about 500 micrometers. In the following examples, a carded hot air bonded nonwoven made of bicomponent fibers was used as the substrate:

[0208] Flat sheet filter media samples were tested at a filtration velocity of 110 fpm. Sample size was 12" x 12". NaCl salt particles ranging from 0.3 to 10 microns were used as the contaminant.

[0209] Example 2

[0210] A carded nonwoven made of 3 denier PET / PE bicomponent fibers was used as the substrate. A composition comprising water, 2-hexyloxyethanol, isopropanolamine, sodium dodecylbenzene sulfonate, lauramine oxide, and ammonium hydroxide was used as the binder. Different nanofiber addition amounts were controlled by adjusting the line speed.

[0211] Table 1

[0212]

[0213]

[0214] This example shows that by controlling the amount of nanoparticles added, the MERV rating can be increased from MERV 7 to MERV 13.

[0215] Example 3

[0216] A high loft hot air bonded carded nonwoven with 5 denier bicomponent fibers was used as the substrate. A typical starch adhesive was diluted and sprayed before nanofiber deposition. The starch fully bonded the nanofibers as the solvent evaporated and dried under an IR heater.

[0217] Table 2

[0218]

[0219] Example 4

[0220] Use spunbond or meltblown media as a substrate, wherein nanoparticles are incorporated into the substrate after IPA discharge, as described herein. Spunbond fibers are made of a molten polymer that is spun and stretched to produce filaments. The average basis weight of the substrate is about 90gsm, and the average thickness is about 0.57mm. Use a base sample without any nanoparticles incorporated. Prepare 4 separate samples, which include nanoparticles incorporated into the substrate, as described herein. In sample 2, nanoparticles are incorporated into meltblown fibers after IPA discharge. In samples 1, 3, and 4, nanoparticles are incorporated into spunbond fibers after IPA discharge. The test results are shown in Table 3 below.

[0221] Table 3

[0222]

[0223]

[0224] As shown, in all three particle groups, the efficiency of the filter media samples incorporating nanoparticles was higher than that of the base samples, and the efficiency of the E2 and E3 particle groups was significantly improved. The overall MERV rating of the samples increased from MERV 7 (base sample) to MERV 12 to MERV 16 (using nanoparticles). The pressure drop of the base sample without nanoparticles was 0.07 inches of water column. The pressure drop of samples 1-4 increased slightly, ranging from 0.17 to 0.41 inches of water column. In sample 2, where nanoparticles were incorporated into meltblown fibers, the MERV rating was 14 and the pressure drop was 0.24 inches of water column.

[0225] Example 5

[0226] A 5 denier hot through bonded carded fiber was used as the substrate. A base sample without nanoparticles incorporated was used. Two separate samples were prepared that included nanoparticles incorporated into the substrate as described herein. The test results are shown in Table 4 below.

[0227] Table 4

[0228]

[0229] As shown, in all three particle groups, the efficiency of the filter media samples incorporating nanoparticles increased significantly compared to the base samples. The overall MERV rating of the samples increased from MERV 6 (base sample) to MERV 13 (with nanoparticles). The pressure drop of the base sample without nanoparticles was 0.03 inches of water column. The pressure drop of samples 1 and 2 increased slightly, ranging from 0.31 to 0.33 inches of water column.

[0230] Example 6

[0231] Meltblown fibers were used as substrates. The average basis weight of the substrate was about 24 gsm and the average thickness was about 0.4 mm. A base sample without nanoparticles or adhesives (e.g., PVOH) was used. Sample 1 included meltblown fibers with the tape side facing up. PVOH was sprayed on the fibers, but nanoparticles were not incorporated. Sample 2 included meltblown fibers with the velvet side facing up. PVOH was sprayed on the fibers, but nanoparticles were not incorporated. Sample 3 included meltblown fibers with PVOH sprayed thereon, and nanoparticles were incorporated into the fibers, as described herein. The test results are shown in Table 5 below.

[0232] Table 5

[0233] sample# Substrate PD E1 E2 E3 MERV Base Meltblown 0.35 82% 96% 99% 14 1 Meltblown 0.38 68% 88% 93% 13 2 Meltblown 0.41 78% 95% 97% 14 3 Meltblown 1.02 92% 99% 99% 15

[0234] As shown, in all three particle groups, especially in the E1 particle group, the efficiency of sample 3 incorporating nanoparticles increased compared to the other three base samples. The overall MERV rating of sample 3 increased from MERV 13 or 14 (base samples) to MERV 15 (using nanoparticles). The PVOH added to samples 2 and 3 did not significantly increase the pressure drop (i.e., 0.35 for the base sample, 0.38 and 0.41 for samples 1 and 2). The pressure drop of sample 3 did increase from about 0.40 inches of water column to about 1 inch of water column. In sample 3, incorporating nanoparticles into the meltblown fiber, the MERV rating was 15 and the pressure drop was 1.02 inches of water column.

[0235] Example 7

[0236] 5 denier hot through bonded carded fibers were used as the substrate. A base sample without nanoparticles was used. Seven additional samples were prepared, which included 5 denier carded fibers with nanoparticles incorporated into the substrate, as described herein. The test results are shown in Table 6 below.

[0237] Table 6

[0238]

[0239]

[0240] As shown, the seven samples incorporating nanoparticles had higher efficiencies than the base samples in all three particle groups, especially in the E2 and E3 particle groups. The overall MERV rating increased from MERV 6 (base sample) to MERV 7 to MERV 13 (with nanoparticles). The pressure drop only increased from 0.03 inches of water column to a maximum of 0.32 inches of water column.

[0241] Example 8

[0242] High loft spunbond fibers were used as substrates in a continuous fiber production line. This test included two different versions: 205-6 and 205-2, where the settings on the continuous fiber production line were changed to produce two substrates with different weights and thicknesses. Each version (205-6 and 205-2) used a base sample without nanoparticles incorporated. Six additional samples were prepared that included 205-6 and 205-2 fibers and nanoparticles incorporated into the substrate, as described herein. The test results are shown in Table 7 below.

[0243] Table 7

[0244] sample# Substrate PD E1 E2 E3 MERV Base 205-6 0.04 0% 9% 43% 6 Base 205-2 0.04 0% 8% 37% 6 1 205-6 0.86 88% 98% 99% 15 2 205-2 0.48 79% 96% 99% 14 3 205-6 0.87 82% 97% 99% 14 4 205-2 0.42 61% 90% 98% 13 5 205-6 0.78 79% 97% 99% 14 6 205-2 0.23 44% 79% 96% 11

[0245] As shown, in all three particle groups, the efficiency of the six samples incorporating nanoparticles increased significantly compared to the base samples. The overall MERV rating increased from MERV 6 (base samples) to MERV 11 to MERV 14 (with nanoparticles). The pressure drop only increased from 0.04 inches of water column to a maximum of 0.87 inches of water column. The pressure drop in the 205-2 sample only increased to a maximum of 0.48 inches of water column.

[0246] Example 9

[0247] Spunbond and meltblown fibers were used as substrates. The average basis weight of the substrate of the spunbond fibers was about 70 gsm, and the average basis weight of the substrate of the meltblown fibers was about 24 gsm. The average thickness of the substrate was about 0.75 mm. A base sample without nanoparticles was used. Five additional samples were prepared, including spunbond and meltblown fibers and nanoparticles incorporated into the fibers, as described herein. In samples 1-3, nanoparticles were sprayed onto meltblown fibers. In samples 4 and 5, nanoparticles were sprayed onto spunbond fibers. In addition, in samples 1 and 2, the adhesive PVOH was not sprayed onto the substrate. PVOH was sprayed onto samples 3-5. The test results are shown in Table 8 below.

[0248] Table 8

[0249] sample# Substrate PD E1 E2 E3 MERV Base Spunbond+MB 0.07 2% 17% 29% 5 1 Spunbond+MB 0.41 100% 100% 100% 16 2 Spunbond+MB 0.56 100% 100% 100% 16 3 Spunbond+MB 0.26 99% 100% 100% 16 4 Spunbond+MB 0.4 100% 100% 100% 16 5 Spunbond+MB 0.17 97% 100% 100% 16

[0250] As shown, in all three particle groups, the efficiency of the five samples incorporating nanoparticles was significantly improved compared to the base samples. The overall MERV rating increased from MERV 5 (base samples) to MERV 16 (with nanoparticles). The pressure drop only increased from 0.07 inches of water column to a maximum of 0.56 inches of water column. In samples 3-5 (PVOH sprayed onto the substrate), the pressure drop only increased to a maximum of 0.4 inches of water column.

[0251] Example 10

[0252] 5 denier hot air bonded carded glass fiber was used as the substrate. A base sample without nanoparticles was used. Three additional samples were prepared, which included 5 denier carded glass fibers and nanoparticles incorporated therein. The test results are shown in Table 9 below.

[0253] Table 9

[0254]

[0255] As shown, in all three particle groups, the efficiency of the three samples incorporating nanoparticles increased significantly compared to the base samples. The overall MERV rating increased from MERV 6 (base samples) to MERV 12 or MERV 13 (with nanoparticles). The pressure drop only increased from 0.03 inches of water column to a maximum of 0.27 inches of water column.

[0256] Embodiment 11

[0257] A fiber blend of 5 denier and 7 denier hot air bonded combed glass fibers was used as the substrate. The medium was hot air bonded. A base sample without nanoparticles was used. Nineteen additional samples were prepared, which included a fiber blend of 5 denier and 7 denier combed glass fibers and nanoparticles incorporated therein. The test results are shown in Table 10 below.

[0258] Table 10

[0259]

[0260]

[0261] As shown, in all three particle groups, all 19 samples incorporating nanoparticles showed significant improvements in efficiency compared to the base samples. The overall MERV rating increased from MERV 6 (base samples) to MERV 10 to MERV 13 (with nanoparticles) (most samples were rated MERV 13). The pressure drop only increased from 0.03 inches of water column to a maximum of 0.31 inches of water column.

[0262] Although these devices, systems and methods have been described in detail herein according to certain preferred embodiments, many modifications and changes may be made thereto by those skilled in the art. Therefore, the foregoing description should not be interpreted as being limited thereto, but rather should be interpreted as including the aforementioned obvious changes, and only limited by the spirit and scope of the appended claims.

[0263] For example, in a first aspect, a first embodiment is a gas filter comprising a first layer of fibers, a second layer of fibers bonded to the first layer, and a plurality of nanoparticles incorporated into the first layer.

[0264] A second embodiment is the first embodiment, wherein the first layer has a first surface and a second surface opposite the first surface, wherein the nanoparticles are disposed through the first surface and into an internal structure between the first surface and the second surface of the first layer.

[0265] A third embodiment is any combination of the first two embodiments, wherein the nanoparticles are incorporated substantially throughout the first layer from the first surface to the second surface.

[0266] A fourth embodiment is any combination of the first three embodiments, wherein the second layer is bonded to the first surface of the first layer.

[0267] A fifth embodiment is any combination of the first four embodiments, wherein the second layer is bonded to the second surface of the first layer.

[0268] A sixth embodiment is any combination of the first five embodiments, further comprising a plurality of nanoparticles incorporated into the second layer.

[0269] A seventh embodiment is any combination of the first six embodiments, wherein the first and second layers each have opposing first and second surfaces, the second surface of the first layer being bonded to the first surface of the second layer.

[0270] An eighth embodiment is any combination of the previous seven embodiments, wherein the nanoparticles are dispersed through the second surface of the first layer and the first surface of the second layer.

[0271] A ninth embodiment is any combination of the first eight embodiments, wherein the nanoparticles form a density gradient from the first surface to the second surface of the first layer.

[0272] A tenth embodiment is any combination of the first nine embodiments, wherein the linear density of the fibers in the first layer is greater than about 3 denier.

[0273] An eleventh embodiment is the tenth embodiment, wherein the linear density of the fibers in the first layer is greater than about 5 denier.

[0274] A twelfth embodiment is any combination of the previous eleven embodiments, wherein the linear density of the fibers in the first layer is greater than about 6 denier.

[0275] A 13th embodiment is any combination of the first 12 embodiments, wherein the linear density of the fibers in the second layer is about 3 denier or less.

[0276] A fourteenth embodiment is any combination of the previous thirteen embodiments, wherein the first layer is laminated to the second layer.

[0277] A fifteenth embodiment is any combination of the previous fourteen embodiments, wherein the fibers in the first layer contain an electrostatic charge.

[0278] A sixteenth embodiment is any combination of the preceding fifteen embodiments, wherein the fibers in the first layer are biocomponent fibers having a core and a sheath, wherein the core and the sheath are non-concentric.

[0279] The 17th embodiment is any combination of the previous 16 embodiments, further comprising a binder within the matrix that binds the nanoparticles to the fibers, wherein the binder comprises a material selected from the group consisting of starch, dextrin, guar gum, PVOH, and synthetic resins.

[0280] An eighteenth embodiment is any combination of the previous seventeen embodiments, further comprising a bonding composition that bonds the nanoparticles to the fibers in the first layer.

[0281] A 19th embodiment is any combination of the previous 18 embodiments, wherein the linear density of the fibers in the first layer is about 7 denier and the linear density of the fibers in the second layer is about 5 denier.

[0282] The twentieth embodiment is any combination of the previous nineteen embodiments, wherein the filter has a MERV rating of at least 13 and a pressure drop of 0.31 inches of water or less.

[0283] In another aspect, the first embodiment is a method for making a filter medium. The method includes providing a first layer and a second layer each comprising fibers, dispersing nanoparticles into a first surface of the first layer so that the nanoparticles at least pass through the first surface of the first layer, and bonding the first layer to the second layer to form a filter medium.

[0284] A second embodiment is the first embodiment, further comprising dispersing the nanoparticles into the first surface of the second layer such that the nanoparticles at least pass through the first surface of the second layer.

[0285] The third embodiment is any combination of the first two embodiments, further comprising bonding the first surface of the first layer to the first surface of the second layer.

[0286] The fourth embodiment is any combination of the first three embodiments, further comprising bonding a second surface of the first layer opposite the first surface of the first layer to a second surface of the second layer opposite the first surface of the second layer.

[0287] The fifth embodiment is any combination of the first four embodiments, further comprising bonding the first surface of the first layer to a second surface of the second layer opposite the first surface of the second layer.

[0288] A sixth embodiment is any combination of the first five embodiments, wherein the second layer is a support layer, wherein the support layer is bonded to the first surface of the layer.

[0289] A seventh embodiment is any combination of the first six embodiments, wherein the second layer is a scrim layer and the support layer is bonded to the first surface of the layer.

[0290] An eighth embodiment is any combination of the previous seven embodiments, further comprising isolating the nanoparticles in the gaseous medium, wherein at least one dimension of the nanoparticles is less than 1 micron.

[0291] A ninth embodiment is any combination of the first eight embodiments, further comprising dispersing nanoparticles substantially throughout the first and second layers to form a composite material.

[0292] The tenth embodiment is any combination of the preceding nine embodiments, wherein the nanoparticles form a gradient within the first layer such that a density of the nanoparticles decreases from a first surface of the first layer to a second surface opposite the first surface.

[0293] An eleventh embodiment is any combination of the preceding ten embodiments, further comprising applying suction to a second surface of the first layer opposite the first surface to cause the single nanoparticle to pass through the first layer.

[0294] A twelfth embodiment is any combination of the first eleven embodiments, further comprising applying a binder to the fibers in the first layer.

[0295] A 13th embodiment is any combination of the previous 12 embodiments, wherein the adhesive is a polymeric adhesive, and further comprising cross-linking the adhesive.

[0296] A fourteenth embodiment is any combination of the previous thirteen embodiments, further comprising laminating the first layer to the second layer.

[0297] In another aspect, the first embodiment is a system for manufacturing a filter medium. The system includes: a feeder for advancing a first layer of fibers from an upstream end to a downstream end; a dispersion device between the upstream end and the downstream end for dispersing nanoparticles into a first surface of the first layer so that the nanoparticles at least pass through the first surface of the first layer; and a device for bonding the first layer to a second layer of fibers.

[0298] The second embodiment is the first embodiment, further comprising a second feeder for advancing the second layer of fibers.

[0299] The third embodiment is any combination of the first two embodiments, further comprising a second dispersing device for dispersing the nanoparticles into the first surface of the second layer so that the nanoparticles at least pass through the first surface of the second layer.

[0300] A fourth embodiment is any combination of the first three embodiments, wherein the first and second feeders are configured such that the first surface of the first layer is bonded to the first surface of the second layer.

[0301] The fifth embodiment is any combination of the first four embodiments, wherein the first and second feeders are configured to feed a second surface of the first layer opposite the first surface of the first layer to a second surface of the second layer opposite the first surface of the second layer.

[0302] A sixth embodiment is any combination of the first five embodiments, wherein the first and second feeders are configured such that a first surface of the first layer is bonded to a second surface of the second layer opposite the first surface of the second layer.

[0303] The seventh embodiment is any combination of the first six embodiments, further comprising a fiberizing device for separating or isolating the nanoparticles in a gaseous medium.

[0304] The eighth embodiment is any combination of the first seven embodiments, further comprising a coating device for distributing adhesive on the fibers in the first layer.

[0305] A ninth embodiment is any combination of the preceding eight embodiments, wherein the coating device comprises a spray device having an outlet proximate an upstream end of the feeder and the nozzle.

[0306] The tenth embodiment is any combination of the first nine embodiments, wherein the feeder comprises a first and an opposing second surface, wherein the first layer is advanced along the first surface, and wherein the system further comprises a negative pressure source adjacent the second surface.

[0307] An eleventh embodiment is any combination of the previous ten embodiments, wherein the thickness of the fibers in the first layer is greater than about 3 denier.

[0308] A twelfth embodiment is any combination of the previous eleven embodiments, wherein the thickness of the fibers in the first layer is greater than about 5 denier.

[0309] A 13th embodiment is any combination of the previous 12 embodiments, wherein the thickness of the fibers in the first layer is greater than about 6 denier.

[0310] A fourteenth embodiment is any combination of the previous thirteen embodiments, wherein the thickness of the fibers in the second layer is 3 denier or less.

Claims

1. A gas filter comprising: The first layer of fibers; a second layer of fibers bonded to said first layer; and A plurality of nanoparticles are incorporated into the first layer. 2 . The filter of claim 1 , wherein the first layer has a first surface and a second surface opposite the first surface, wherein the nanoparticles are disposed through the first surface and into an internal structure between the first surface and the second surface of the first layer.

3. The filter of claim 2, wherein the nanoparticles are incorporated substantially throughout the first layer from the first surface to the second surface. The filter of claim 2 , wherein the second layer is bonded to the first surface of the first layer.

5. The filter of claim 2, wherein the second layer is bonded to the second surface of the first layer.

6. The filter of claim 1, further comprising a plurality of nanoparticles incorporated into the second layer.

7. The filter of claim 6, wherein the first and second layers each have opposing first and second surfaces, the second surface of the first layer being bonded to the first surface of the second layer.

8. The filter of claim 7, wherein the nanoparticles are dispersed across the second surface of the first layer and the first surface of the second layer.

9. The filter of claim 2, wherein the nanoparticles form a density gradient from the first surface to the second surface of the first layer.

10. The filter of claim 1 wherein the fibers in the first layer have a linear density greater than about 3 denier.

11. The filter of claim 1 , wherein the fibers in the first layer have a linear density greater than about 5 denier.

12. The filter of claim 1, wherein the fibers in the first layer have a linear density greater than about 6 denier.

13. The filter of claim 1, wherein the fibers in the second layer have a linear density of about 3 denier or less.

14. The filter of claim 1, wherein the linear density of the fibers in the first layer is about 7 denier and the linear density of the fibers in the second layer is about 5 denier.

15. The filter of claim 14, wherein the filter has a MERV rating of at least 13 and a pressure drop of 0.31 inches of water or less.

16. The filter of claim 1, wherein the first layer is laminated to the second layer.

17. The filter of claim 1, wherein the fibers in the first layer contain an electrostatic charge.

18. The filter of claim 10, wherein the fibers in the first layer are biocomponent fibers having a core and a sheath, wherein the core is non-concentric with the sheath.

19. The filter of claim 1, further comprising a binder within the substrate, the binder binding the nanoparticles to the fibers, wherein the binder comprises a material selected from the group consisting of starch, dextrin, guar gum, PVOH, and synthetic resins.

20. The filter of claim 1, further comprising a binding composition that binds the nanoparticles to fibers in the first layer.

21. A method for making a filter medium, the method comprising: providing a first layer and a second layer each comprising fibers; Dispersing nanoparticles into the first surface of the first layer such that the nanoparticles at least pass through the first surface of the first layer; as well as The first layer is bonded to the second layer to form a filter media.

22. The method of claim 21, further comprising dispersing the nanoparticles into the first surface of the second layer such that the nanoparticles penetrate at least the first surface of the second layer.

23. The method of claim 22, further comprising bonding the first surface of the first layer to the first surface of the second layer.

24. The method of claim 22, further comprising bonding a second surface of the first layer opposite the first surface of the first layer to a second surface of the second layer opposite the first surface of the second layer.

25. The method of claim 22, further comprising bonding a first surface of the first layer to a second surface of the second layer opposite the first surface of the second layer.

26. The method of claim 21, wherein the second layer is a support layer, wherein the support layer is bonded to the first surface of the layer.

27. The method of claim 21, wherein the second layer is a scrim layer, wherein the support layer is bonded to the first surface of the layer.

28. The method of claim 21, further comprising isolating the nanoparticles in a gaseous medium, wherein at least one dimension of the nanoparticles is less than 1 micron.

29. The method of claim 21, further comprising dispersing the nanoparticles substantially throughout the first and second layers to form a composite material.

30. The method of claim 21, wherein the nanoparticles form a gradient within the first layer such that a density of the nanoparticles decreases from a first surface of the first layer to a second surface opposite the first surface.

31. The method of claim 21, further comprising applying suction to a second surface of the first layer opposite the first surface to draw individual nanoparticles through the first layer.

32. The method of claim 21 further comprising applying a binder to the fibers in the first layer.

33. The method of claim 32, the adhesive being a polymeric adhesive, and further comprising cross-linking the adhesive.

34. The method of claim 21 further comprising laminating the first layer to the second layer.

35. A system for manufacturing a filter medium, the system comprising: a feeder for advancing a first layer of fibers from an upstream end to a downstream end; a dispersion device between the upstream end and the downstream end for dispersing nanoparticles into the first surface of the first layer so that the nanoparticles at least pass through the first surface of the first layer; and Means for bonding said first layer to a second layer of fibers.

36. The system of claim 35, further comprising a second feeder for advancing a second layer of fibers.

37. The system of claim 36, further comprising a second dispersing device for dispersing nanoparticles into the first surface of the second layer such that the nanoparticles at least pass through the first surface of the second layer.

38. The system of claim 37, wherein the first feeder and the second feeder are configured such that the first surface of the first layer is bonded to the first surface of the second layer.

39. The system of claim 37, wherein the first feeder and the second feeder are configured to pass a second surface of the first layer opposite to a first surface of the first layer to a second surface of the second layer opposite to the first surface of the second layer.

40. The system of claim 37, wherein the first feeder and the second feeder are configured such that a first surface of the first layer is bonded to a second surface of the second layer opposite the first surface of the second layer.

41. The system of claim 35, further comprising a fiberizing device for separating or isolating the nanoparticles in a gaseous medium.

42. The system of claim 35, further comprising a coating device for dispensing an adhesive on the fibers in the first layer.

43. The system of claim 42, wherein the coating device comprises a spray device having an outlet proximate an upstream end of the feeder and a nozzle.

44. The system of claim 35, wherein the feeder comprises first and second opposing surfaces, wherein the first layer is advanced along the first surface, wherein the system further comprises a source of negative pressure adjacent the second surface.

45. The system of claim 35, wherein the fibers in the first layer have a thickness greater than about 3 denier.

46. ​​The system of claim 35, wherein the fibers in the first layer have a thickness of at least about 5 denier.

47. The system of claim 35, wherein the fibers in the first layer have a thickness of at least about 6 denier.

48. The system of claim 35, wherein the fibers in the second layer have a thickness of 3 denier or less.